Hydrogen reservoir
By using a combination of barrier materials and fiber reinforced materials to form the wall of the hydrogen storage, the problems of excessive weight and high hydrogen permeability of the existing hydrogen storage are solved, and hydrogen with low weight and low hydrogen permeability is achieved. Storage, for mobile applications.
Patent Information
- Application Number
- CN202380045385.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-05
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-21
AI Technical Summary
Existing hydrogen reservoirs have challenges in weight and hydrogen permeability, especially in mobile applications where they are overweight and have high hydrogen permeability.
A combination of barrier materials and reinforcing materials is used. The reinforcing materials can be fiber materials, such as carbon fibers, silicon carbide fibers, etc., used to make the walls of the hydrogen storage to reduce weight and hydrogen permeability.
Achieved low weight and low hydrogen permeability hydrogen storage suitable for mobile applications, especially in the vehicle and aerospace fields.
Smart Images

Figure CN119343322A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hydrogen storage device with low weight and low hydrogen permeability. The present invention also relates to a composite material comprising a barrier material and a reinforcing material. The composite material can be used as a wall in a molecular hydrogen storage device. Background Art
[0002] There are four main technologies for storing hydrogen:
[0003] High voltage technology;
[0004] Cryogenic technology (liquid hydrogen);
[0005] ·Cryogenic compression technology;
[0006] Chemical adsorption or adsorption techniques.
[0007] High pressure is generally understood here to mean up to 700 bar, see Materials 2019, 12, 1973, wherein up to 1000 bar should be used, see Int. J. Hydrogen Energy Mar. 2017, 42 (11): 7254-62. Depending on the pressure, the required compression of hydrogen consumes 10%-15% of the energy to be stored, see Int. J. of Hydrogen Energy 2021, 46 (29), 15671-15690.
[0008] In steel design, the relevant tanks typically have dimensions and operating pressures of 220 mm diameter, 9.1 mm wall thickness, 280 bar operating pressure or 470 mm diameter, 26 mm wall thickness, 410 bar operating pressure, see International Journal of Hydrogen Energy 2017, 42 (19), 13777-13788. Typical material problems occurring in pressure vessels with metal components involve hydrogen embrittlement of the metal, see International Int. J. of Hydrogen Energy 2021, 46 (29), 15671-15690.
[0009] In current type IV hydrogen storage devices, in order to reduce weight, mechanical strength is ensured by replacing metal with a carbon fiber structure, see Materials 2019, 12, 1973. The carbon fiber structure must in turn be connected to a barrier material, the so-called "liner", for example by coating or lamination, whose hydrogen permeability is naturally crucial. Therefore, another typical material problem of this hydrogen storage device is that the material composites currently used will dissolve, especially when suddenly unloaded (mechanical and thermal reasons: temperature changes during compression and decompression), see Int. J. Hydrogen Energy 2018, 43 (9), 4671-4680.
[0010] High-voltage technology is one of the storage technologies generally favored by mobile applications, see Materials 2019,12,1973.
[0011] N. Schramm, M. Neubert, MD Naumann, L. Ulke-Winter, L. Kroll and S. Nendel, Entwicklung eines zur Wasserstoffspeicherung, Fuel Cell Conference FC3, Chemnitz, 26.-27.11.2019 describes a prototype whose wall comprises a 4 mm thick "liner" made of PE, to which a CFK bushing with an average thickness of 13.5 mm is connected outwardly. The term "CFK" stands for "carbon fiber reinforced plastic". Typical values for the performance of such systems can be obtained from Yu Sun, Hong Lv, Wei Zhou, Cunman Zhang, Research on hydrogen permeability of polyamide 6 as the liner material for type IV hydrogen storage tank, International Journal of Hydrogen Energy 45 (2020) 24980-24990. For example, in this article, the barrier effect of a 4 mm thick "liner" made of PA6 (polycaprolactam, well-known trademark "Perlon") is examined. The pressure dependence of the barrier effect is also taken into account here. At room temperature and a single-sided load of 25 MPa, the permeability is 5.6×10 -16 mol / (m·s·Pa); when the single-side loading is 50MPa, the permeability is 1.4×10 -16 mol / (m·s·Pa). Therefore, the H2 flow through the 4 mm thick "liner" is 3.5×10 -6 mol / (m2 ·s), and in the second case it is 1.8×10 -6 mol / (m 2 ·s). For comparison, Sun et al. gave a maximum permeability of 1.24·10 for materials suitable for “lining” based on ISO 19881-2018 cited by these authors. -15 mol / (m·s·Pa). Sun et al. also described a PA6 "liner" with fillers.
[0012] RRBarth, KL Simmons, C. San Marchi, Polymers for Hydrogen Infrastructure and Vehicle Fuel Systems: Applications, Properties, and Gap Analysis, Sandia Report SAND2013-8904 (Sandia National Laboratory, USA) provides a review of various "liner" materials. However, basically only high-density polyethylene (HDPA) and polyamide (PA) are used, see Winoj Balasooriya, Clara Clute, Bernd Schrittesser, and Gerald Pinter, A Review on Applicability, Limitations, and Improvements of Polymeric Materials in High-Pressure Hydrogen Gas Atmospheres, Polymer Reviews, Vol. 62, No. 1, 2022, 175-209.
[0013] The disadvantage of the second technology mentioned above (i.e., cryogenic technology) is that the energy consumption for liquefying hydrogen at the beginning of storage is significantly greater than that of high-pressure technology, up to 40% of the stored energy, and the temperature must be kept below -253°C, see Int. J. Hydrogen Energy Mar. 2017, 42 (11): 7254-62. A pressure vessel with an additional insulation layer is used. This technology is of great significance for stationary systems, in which such insulation layers can be designed so that the losses caused by evaporation ("boil-off") through the safety valve due to the inevitable heat inflow are very low, see Materials 2019, 12, 1973 or for applications where high energy density is crucial, such as space travel, see Int. J. Hydrogen Energy Mar. 2017, 42 (11): 7254-62 or aviation, see Materials 2019, 12, 1973.
[0014] The above-mentioned pressure vessel is constructed in cryogenic compression technology so that it can also withstand high pressures of, for example, up to 300 bar, which significantly reduces evaporation losses compared to cryogenic technology (at the same temperature), see Int. J. Hydrogen Energy Mar. 2017, 42 (11): 7254-62. Cryogenic compression storage can also be operated at a lower temperature but above the boiling point of hydrogen, see Int. J. Hydrogen Energy Mar. 2017, 42 (11): 7254-62. Compared with storage at room temperature, this takes advantage of the fact that for gases at the same pressure, the amount of substance is inversely proportional to the temperature, thereby increasing the amount of hydrogen stored per unit volume. As with high-pressure storage at room temperature, such pressure vessels can be built using carbon fiber technology and equipped with corresponding "linings", see Int. J. Hydrogen Energy Mar. 2017, 42 (11): 7254-62.
[0015] There are various methods in the field of chemical adsorption or adsorption. One involves the combination of hydrogen with magnesium under special pressure and temperature conditions and the corresponding storage of magnesium hydride, see Materials 2019, 12, 1973. In addition to the energy loss associated with the process, there is also a standard enthalpy of formation of the hydride, but this standard enthalpy is only about 10% of the combustion enthalpy of hydrogen. Storage in low-pressure containers, for example in containers at 15 bar, see Int. J. Hydrogen Energy 2010, 35 (12), 6311-6322, where the pressure should counteract the dissociation of the hydride. Summary of the invention
[0016] The object of the invention is to improve the storage of hydrogen. This object is achieved by the subject matter of the claims.
[0017] The invention relates to a hydrogen storage device, in particular a mobile hydrogen storage device, which is used, for example, in a motor vehicle (in particular for a passenger car (Pkw), for a truck (Lkw), for a bus or for a motorcycle), in a rail vehicle (in particular a passenger train or a freight train), in an aircraft (in particular an airplane or a helicopter) or in a ship (in particular a passenger ship, a container ship or a tanker). The mobile hydrogen storage device can be, in particular, a hydrogen tank or an adsorption storage device.
[0018] In the course of efforts to further move away from fossil fuels such as coal, oil or gas, the use of hydrogen is a future technology with great growth potential. However, especially in the case of mobile hydrogen storages that can be used in all types of vehicles, it is very important to keep the weight of the hydrogen storage low to ensure good efficiency of this technology. Very heavy mobile hydrogen storages are disadvantageous because the weight of the hydrogen storage always has to be transported along, which is accompanied by increased energy consumption.
[0019] In this context, the present invention provides a low-weight hydrogen storage. The hydrogen storage of the present invention includes a composite material, which includes a barrier material and a reinforcing material. The reinforcing material can be a fiber material in particular. The reinforcing material can in particular contain carbon fibers, silicon carbide fibers, aluminum oxide fibers, silicon oxide fibers, or a combination of two or more thereof or consist of these. Carbon fibers, silicon fibers, etc., in particular, refer to carbon, silicon carbide, etc. as their respective main components, that is, they account for a proportion of the total weight of the fiber greater than 50% by weight, more preferably greater than 60% by weight, more preferably greater than 70% by weight, more preferably greater than 80% by weight, more preferably greater than 90% by weight, more preferably greater than 95% by weight, more preferably greater than 98% by weight, more preferably greater than 99% by weight, more preferably 100% by weight or substantially 100% by weight; in addition to carbon, silicon carbide, etc., the fiber may also in particular contain one or more components selected from the group consisting of oxygen, boron, titanium, zirconium, nitrogen, and a combination of two or more thereof.
[0020] The reinforcing material may also include glass fibers, such as are used for glass-fiber reinforced plastics; the corresponding glasses are often referred to as E-glass, S-glass, R-glass, M-glass, C-glass, ECR-glass, D-glass, AR-glass or Q-glass.
[0021] The reinforcing material can be a fiber-reinforced plastic, such as carbon fiber reinforced plastic (CFRP) or glass fiber reinforced plastic (GFRP). Fiber-reinforced plastic is a material made of reinforcing fibers and a plastic matrix. Fiber volume fraction Preferably in the range of 50 to 70% by volume, in particular 55 to 65% by volume or about 60% by volume. Preferably at least 50% by volume, at least 55% by volume or at least 60% by volume. Preferably, it is at most 70% by volume, at most 65% by volume or preferably at most 60% by volume. The plastic matrix preferably comprises an epoxy resin or consists of an epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A substantially super-elliptical shaped hydrogen storage tank 11 is schematically shown, having a wall made of a composite material.
[0023] Figure 2 A generally super-elliptical shaped hydrogen storage 21 is schematically shown, having a wall portion partially made of a composite material.
[0024] Figure 3 Two bottle-shaped hydrogen storage tanks 31 a and 31 b are schematically shown, which have a wall made completely or partially from a composite material. DETAILED DESCRIPTION
[0025] On the one hand, the invention relates to a hydrogen storage device, in particular a mobile hydrogen storage device, preferably a mobile hydrogen tank. The invention provides a hydrogen storage device which is particularly lightweight but which (more precisely: its wall) has a particularly low hydrogen permeability.
[0026] The hydrogen storage device of the present invention preferably has a cavity in which hydrogen can be stored. The cavity is surrounded by a wall. The wall should prevent hydrogen leakage. The thickness of the wall is in particular in the range of 15 mm to 50 mm, for example in the range of 20 mm to 45 mm, 25 mm to 40 mm or 30 mm to 35 mm. The thickness of the wall should not be too small. Otherwise, unnecessary loss of hydrogen may be too large. The thickness of the wall is preferably at least 15 mm, at least 20 mm, at least 25 mm or at least 30 mm. But the thickness of the wall should not be too large. Otherwise, the weight of the hydrogen storage device will be unnecessarily increased. This plays an important role in mobile hydrogen storage devices, such as hydrogen tanks. The thickness of the wall is preferably at most 50 mm, at most 45 mm, at most 40 mm or at most 35 mm.
[0027] The wall section has in particular at least one opening, for example at least one inlet and / or at least one outlet. The inlet and / or the outlet can be arranged in two separate openings or in one common opening. The inlet is used to fill the cavity with hydrogen. The hydrogen can leave the cavity through the outlet, for example to an energy converter, in particular a fuel cell. For example, the hydrogen can be used as a fuel from which the energy converter can obtain electrical energy, in particular for driving a vehicle. The opening of the wall section is preferably provided with a valve. This allows the entry of hydrogen into the cavity and the discharge of hydrogen from the cavity to be controlled in a targeted manner.
[0028] Hydrogen storage, such as hydrogen tank, is a container with a cavity in which hydrogen can be stored. The present invention relates to such a container with a wall containing a barrier material. The container or its wall can have an inlet and / or an outlet. The container is a hydrogen storage (preferably a mobile hydrogen storage or hydrogen tank) or can be used as a hydrogen storage (preferably as a mobile hydrogen storage or hydrogen tank). The container or its wall can be made of a barrier material. However, the wall preferably includes one or more other materials, in particular one or more reinforcing materials. The composite material containing a barrier material and a reinforcing material or composed of a barrier material and a reinforcing material can exist as a material composite or a composite material, in particular, it can also exist as a laminated structure. Therefore, the material composite is a layered composite. The composite material of the present invention is preferably a material composite, in particular a layer composite, which preferably contains or consists of one or more barrier material layers and one or more reinforcing material layers. Unlike a material composite, a composite material should be understood as a composite material that does not have such a layer structure or other macroscopically identifiable composite structures, such as a dispersed reinforced plastic or glass ceramic. The use of a reinforcing material can match the load conditions in the container.
[0029] In some embodiments of the invention, the entire wall of the hydrogen storage device comprises a composite material, which comprises or consists of a barrier material and a reinforcing material. The entire wall can also consist of a composite material, which comprises or consists of a barrier material and a reinforcing material. The advantage of this design is that the wall has a special mechanical stability. However, this design can also be disadvantageous, especially when there are very high requirements for a particularly low weight.
[0030] In some embodiments of the invention, only a portion of the wall comprises a composite material, which comprises or consists of a barrier material and a reinforcing material. A portion of the wall may also consist of a composite material, which comprises or consists of a barrier material and a reinforcing material. The portion of the wall that does not comprise a composite material may, for example, consist of a barrier material. Additional weight savings can be achieved by this design. In particular, reinforcing material can be omitted at locations of the wall where the barrier material already has a relatively high stability due to the geometric design.
[0031] Preferably, the wall comprises a barrier material and a reinforcing material, for example fibers or fiber-containing reinforcing materials, in particular containing carbon fibers or consisting of carbon fibers, for example a carbon fiber braid, and / or silicon carbide fibers and / or aluminum oxide or silicon oxide fibers, at least partially or over the entire wall. In an embodiment of the invention, the container or the wall comprises a barrier material (in particular having a cylindrical basic shape) as a winding core of a fiber braid, in particular comprising carbon fibers and / or silicon carbide fibers or consisting of carbon fibers and / or silicon carbide fibers. The container can be a fixed container or a mobile container. The mobile container is, for example, a tank for a vehicle, in particular a motor vehicle (in particular for a passenger car (Pkw), for a truck (Lkw), for a bus or for a motorcycle), for a rail vehicle (in particular for a passenger train or for a freight train), for an aircraft (in particular for an airplane or for a helicopter) or for a ship (in particular for a passenger ship, a container ship or a tanker).
[0032] The term “hydrogen tank” particularly refers to a mobile hydrogen storage, for example for a vehicle.
[0033] The container of the invention has in particular a cavity surrounded by a wall. The thickness of the wall is in particular in the range of 15 mm to 50 mm, for example in the range of 20 mm to 45 mm, 25 mm to 40 mm or 30 to 35 mm. The thickness of the wall is preferably at least 15 mm, at least 20 mm, at least 25 mm or at least 30 mm. The thickness of the wall is preferably at most 50 mm, at most 45 mm, at most 40 mm or at most 35 mm.
[0034] The thickness of the wall can be designed to be uniform over the entire wall. It is also possible for the wall to be designed thicker precisely in areas where special reinforcement is required than in areas where such reinforcement is not required. Such deviations in the thickness of the wall can be achieved, for example, by correspondingly adjusting the thickness of the barrier material. However, the thickness of the barrier material is preferably not of spatially variable size, since otherwise "diffusion holes", i.e. areas with a greater permeability to hydrogen, would result. Preferably, the thickness variation mentioned is based on the fact that a thicker layer of reinforcement material is provided or that no layer of reinforcement material is provided at all.
[0035] The difference between the maximum thickness and the minimum thickness of the wall portion may also be referred to as the total thickness variation of the wall portion. The total thickness variation of the wall portion is preferably in the range of 0.1 to 10 mm, for example in the range of 0.2 to 5.0 mm or 0.5 to 2.0 mm. The total thickness variation of the wall portion may be, for example, at least 0.1 mm, at least 0.2 mm or at least 0.5 mm. The total thickness variation of the wall portion may, for example, be at most 10 mm, at most 5.0 mm or at most 2.0 mm.
[0036] The wall has an inner surface and an outer surface. The inner surface is in contact with the cavity and therefore, in the case of filling, also with the hydrogen located therein. The outer surface of the wall is correspondingly directed outwards and is therefore separated from the cavity and any hydrogen located therein by the thickness of the wall.
[0037] According to the structure, the wall has an inner layer in any case. The inner layer is in particular a layer that provides the inner surface of the wall. The wall can consist completely of the inner layer or of the inner layer in specific areas, so that the inner layer provides the inner surface and the outer surface of the wall, for example in areas where no additional reinforcement is present. In the case of a completely single-layer embodiment, a composite material comprising or consisting of a barrier material and a reinforcement material is preferably used. Such a composite material can combine the functions of a barrier material and the functions of a reinforcement material.
[0038] However, in addition to the inner layer, the wall preferably also has an outer layer. In such an embodiment, the inner surface of the wall is provided by the inner layer and the outer surface of the wall is provided by the outer layer.
[0039] The inner layer preferably comprises or consists of a barrier material.
[0040] The inner layer of the present invention is in particular a planar material and is therefore not fibrous. The fibrous design of the inner layer is associated with an increased hydrogen permeability, which is to be avoided according to the present invention. On the contrary, the hydrogen permeability should be lower. Therefore, the inner layer is preferably not fibrous. On the contrary, a planar design of the inner layer is preferred. The inner layer is preferably designed in a layered manner, for example in the form of a film or a layer. Therefore, the inner layer is preferably in the form of a layer, in particular in the form of a film or a layer. Preferably, the inner layer is substantially free of pores, gaps and / or holes. Preferably, the inner layer is a closed layer.
[0041] The inner layer preferably has a thickness in the range of 0.02 mm to 5.0 mm, for example 0.05 to 3.5 mm, 0.1 to 2.5 mm, 0.2 to 2.0 mm or 0.5 to 1.2 mm. The thickness of the inner layer is preferably at least 0.02 mm, at least 0.05 mm, at least 0.1 mm, at least 0.2 mm or at least 0.5 mm. The thickness of the inner layer is preferably at most 5.0 mm, at most 3.5 mm, at most 2.5 mm, at most 2.0 mm or at most 1.2 mm.
[0042] The difference between the maximum thickness and the minimum thickness of the inner layer can also be referred to as the total thickness variation of the inner layer. The total thickness variation of the inner layer is preferably in the range of 0.005mm to 1.0mm, for example, in the range of 0.01 to 0.75mm, 0.02 to 0.5mm or 0.05 to 0.25mm. The total thickness variation of the inner layer is preferably at least 0.005, at least 0.01mm, at least 0.02mm or at least 0.05mm. The total thickness variation of the inner layer is preferably at most 1.0mm, at most 0.75mm, at most 0.5mm or at most 0.25mm.
[0043] The outer layer preferably comprises a reinforcing material or consists of a reinforcing material. The outer layer preferably has a thickness in the range of 10 mm to 35 mm, for example 15 to 30 mm or 20 to 25 mm. The thickness of the outer layer is preferably at least 10 mm, at least 15 mm or at least 20 mm. The thickness of the outer layer is preferably at most 35 mm, at most 30 mm or at most 25 mm.
[0044] The difference between the maximum thickness and the minimum thickness of the outer layer can also be referred to as the total thickness variation of the outer layer. The total thickness variation of the outer layer is preferably in the range of 0.1 mm to 10 mm, for example in the range of 0.2 to 5.0 mm or 0.5 to 2.5 mm. The total thickness variation of the outer layer is preferably at least 0.1 mm, at least 0.2 mm or at least 0.5 mm. The total thickness variation of the outer layer is preferably at most 10 mm, at most 5.0 mm or at most 2.5 mm.
[0045] The volume of the cavity is in particular in the range of 20 liters to 100,000 liters, preferably 50 liters to 50,000 liters, for example 100 to 25,000 liters, 200 to 10,000 liters, 500 to 5,000 liters or 1,000 to 2,000 liters. The volume of the cavity is preferably at least 20 liters, more preferably at least 50 liters, for example at least 100 liters, at least 200 liters, at least 500 liters or at least 1,000 liters.
[0046] The volume of the cavity is preferably at most 100,000 litres, more preferably at most 50,000 litres, for example at most 25,000 litres, at most 10,000 litres, at most 5,000 litres or at most 2,000 litres.
[0047] The container and in particular the boundaries of the cavity (ie the walls) can have different shapes. Preferably, a super-ellipsoidal or substantially super-ellipsoidal shape such as Figure 1 and Figure 2 As shown in the example in FIG. Superellipsoidal or substantially superellipsoidal shapes are particularly advantageous for withstanding high pressures. The same applies to bottle-shaped designs, which are also part of the present invention. For example Figure 3A bottle-shaped design is shown. In principle, complex shapes are possible (and are also possible in practice). The transition from one shape to another is usually fluid. For example, a cylindrical basic shape with a curvature on one side can be called a bottle shape.
[0048] The invention relates in particular to a hydrogen storage device having a wall surrounding a cavity. In a preferred embodiment, the wall consists of a composite material, in particular a material composite, which comprises an inner (i.e., facing the cavity) barrier layer containing or consisting of a barrier material and an outer reinforcement layer containing or consisting of a reinforcement material. The reinforcement layer can in particular be arranged continuously around the barrier layer.
[0049] The hydrogen storage device may include one or more valves, for example two valves. The valves may in particular be arranged on opposite sides of the hydrogen storage device, for example on the short sides of the hydrogen storage device.
[0050] The hydrogen storage device or its wall can be designed in particular so that the shape of the wall is based on a cylindrical shape or on a cylindrical basic shape. Various shapes can be presented based on the cylindrical basic shape, such as a superelliptical or substantially superelliptical shape or a bottle shape. In the case of a superelliptical or substantially superelliptical shape, two short sides are particularly provided, which are completely or partially convexly curved, wherein the middle of the short side can be a flat surface. For a bottle shape, one of the short sides is always designed as the bottom on which a bottle-shaped hydrogen storage device can be placed. The other short side can be convexly curved at will. In a bottle-shaped embodiment, the valve is preferably arranged on an arbitrarily convexly curved short side, and the short side can be constructed at the end of the hydrogen storage device opposite to the bottom. The bottle-shaped embodiment preferably contains only one valve.
[0051] In a single valve solution, the valve can be set as an inlet and an outlet in particular. In a double valve solution, for example, in a superelliptical or substantially superelliptical shape of a hydrogen storage device having two opposite convexly curved short sides, the two valves can be set in particular on the two short sides, that is, one valve is set on each of the two short sides. For example, in a multi-valve solution such as a double valve solution, one of the valves can be provided as an inlet and the other valve as an outlet. However, this is not necessarily the case. Even if a multi-valve solution, such as a double valve solution, is adopted, one of the valves can be provided as an inlet and an outlet. The other valve (in a double valve solution) or the other valve (in an embodiment with three or more valves) can also be designed as an inlet and / or an outlet. One or more valves can also be designed as a safety valve. For example, a safety valve can be equipped with a pressure sensor and open when a pressure threshold is exceeded to prevent the construction of an unexpected overpressure. "Unexpected overpressure" should be understood in particular as a pressure that can be accompanied by damage to the integrity of the wall of the hydrogen storage device, wherein a relevant amount of hydrogen in the cavity can be gradually or even spontaneously lost. Spontaneous losses may also create a risk of damage to nearby objects or building parts or injury to nearby persons. Therefore, an undesired build-up of overpressure should preferably be avoided.
[0052] The target overpressure required for the stored hydrogen and which can be set in a targeted manner should not be confused with this undesired overpressure. In order to be able to withstand such a target overpressure, high demands are placed on the material of the wall of the hydrogen storage tank.
[0053] The container of the present invention is particularly suitable for storing hydrogen. For this purpose, the container must be able to withstand high or very high pressures, as described above. The container preferably withstands pressures of up to 10 bar, up to 25 bar, up to 50 bar, up to 100 bar, up to 200 bar, up to 300 bar, up to 400 bar, up to 500 bar, up to 600 bar, up to 700 bar, up to 800 bar, up to 900 bar, up to 1000 bar, up to 1200 bar or up to 1500 bar.
[0054] The wall of the hydrogen storage device preferably comprises or consists of a composite material, in particular a composite material or a material composite.
[0055] The present invention further relates to a composite material, in particular a composite material or a material composite, in particular a composite material or a material composite comprising or consisting of a barrier material and a reinforcing material.
[0056] The density of the reinforcing material is preferably between 1.4 and 4.5 g / cm 3 , for example 1.5g / cm 3 Up to 3.5g / cm 3 , 1.6 to 3.0 g / cm3 or 1.7 to 2.5 g / cm 3 The density of the reinforcing material is preferably at least 1.4 g / cm 3 , at least 1.5g / cm 3 , at least 1.6g / cm 3 or at least 1.7g / cm 3 The density of the reinforcing material is preferably at most 4.5 g / cm 3 , up to 3.5g / cm 3 , up to 3.0g / cm 3 or up to 2.5g / cm 3 .
[0057] The ratio of the coefficient of thermal expansion of the barrier material to the reinforcing material is also important. The difference between the average coefficient of thermal expansion (CTE) of the reinforcing material and the barrier material in the range of 20°C to 300°C is preferably in the range of 0.0 to 10.0 ppm / K, 0.1 to 7.5 ppm / K, 0.2 to 5.0 ppm / K, 0.5 to 2.5 ppm / K or 1.0 to 2.0 ppm / K. The difference between the CTE of the reinforcing material and the CTE of the barrier material is preferably at most 10.0 ppm / K, at most 7.5 ppm / K, at most 5.0 ppm / K, at most 2.5 ppm / K or at most 2.0 ppm / K. The difference between the CTE of the reinforcing material and the CTE of the barrier material may be, for example, about 0.0 ppm / K, at least 0.1 ppm / K, at least 0.2 ppm / K, at least 0.5 ppm / K or at least 1.0 ppm / K. "Differential" is understood to mean in particular the difference between the CTE of the reinforcement material and the CTE of the barrier material or the amount of this difference.
[0058] When "CTE" is referred to in this disclosure, unless otherwise specified, it refers to the average linear coefficient of thermal expansion in the range of 20° C. to 300° C. This applies to both measured and calculated values.
[0059] The reinforcing material is used particularly for mechanical reinforcement and therefore preferably has excellent mechanical properties.
[0060] For example, the reinforcing material may have a tensile strength in the range of 1.5 GPa to 8.0 GPa, for example 2.0 to 6.0 GPa, 2.5 to 5.0 GPa or 3.0 to 4.0 GPa. The tensile strength of the reinforcing material is preferably at least 1.5 GPa, at least 2.0 GPa, at least 2.5 GPa or at least 3.0 GPa. The tensile strength of the reinforcing material may be, for example, at most 8.0 GPa, at most 6.0 GPa, at most 5.0 GPa or at most 4.0 GPa.
[0061] The reinforcing material can for example have an elastic modulus of 120GPa to 500GPa, for example 150 to 450GPa, 170 to 420GPa, 200 to 400GPa, 220 to 380GPa or 250 to 350GPa. The elastic modulus of the reinforcing material can for example be at least 120GPa, at least 150GPa, at least 170GPa, at least 200GPa, at least 220GPa or at least 250GPa. The elastic modulus of the reinforcing material can for example be at most 500GPa, at most 450GPa, at most 420GPa, at most 400GPa, at most 380GPa or at most 350GPa.
[0062] The tensile strength, the modulus of elasticity and other material characteristics can be determined in a method known as the tensile test (also called the tensile test). The result of the tensile test is a stress-strain diagram. Technical material characteristic parameters can be read from it. Depending on the material to be tested, the tensile test is described in different standards known to the person skilled in the art. The tensile properties of ceramic fibers can be determined in particular according to DIN EN 1007-4:2004-08.
[0063] The reinforcement material may, for example, have an average linear coefficient of thermal expansion (CTE) in the range of -1.0 to 20.0 ppm / K, -0.5 to 15.0 ppm / K, or -0.2 to 12.0 ppm / K. For example, the CTE may be at least -1.0 ppm / K, at least -0.5 ppm / K, or at least -0.2 ppm / K. For example, the CTE may be at most 20.0 ppm / K, at most 15.0 ppm / K, or at most 12.0 ppm / K.
[0064] For fibrous reinforcement materials, the CTE in the longitudinal direction may be different from the CTE in the transverse direction. In particular, the CTE in the longitudinal direction may be close to zero or even negative. However, the CTE in the transverse direction may be significantly greater than the CTE in the longitudinal direction.
[0065] The CTE in the lateral direction is preferably in the range of 2.0 to 20.0 ppm / K, 5.0 to 15.0 ppm / K, or 7.5 to 12.5 ppm / K. For example, the CTE in the lateral direction may be at least 2.0 ppm / K, at least 5.0 ppm / K, or at least 7.5 ppm / K. For example, the CTE in the lateral direction may be at most 20.0 ppm / K, at most 15.0 ppm / K, or at most 12.5 ppm / K.
[0066] The CTE in the longitudinal direction is preferably in the range of -1.0 to 1.0 ppm / K, -0.5 to 0.5 ppm / K, or -0.2 to 0.0 ppm / K. For example, the CTE in the longitudinal direction may be at least -1.0 ppm / K, at least -0.5 ppm / K, or at least -0.2 ppm / K. For example, the CTE in the longitudinal direction may be at most 1.0 ppm / K, at most 0.5 ppm / K, or at most 0.0 ppm / K.
[0067] The difference between the CTE of the reinforcing material in the transverse direction and the CTE of the barrier material is preferably in the range of 0.0 to 10.0 ppm / K, 0.1 to 7.5 ppm / K, 0.2 to 5.0 ppm / K, 0.5 to 2.5 ppm / K or 1.0 to 2.0 ppm / K. The difference between the CTE of the reinforcing material in the transverse direction and the CTE of the barrier material is preferably at most 10.0 ppm / K, at most 7.5 ppm / K, at most 5.0 ppm / K, at most 2.5 ppm / K or at most 2.0 ppm / K. The difference between the CTE of the reinforcing material in the transverse direction and the CTE of the barrier material may be, for example, about 0.0 ppm / K, at least 0.1 ppm / K, at least 0.2 ppm / K, at least 0.5 ppm / K or at least 1.0 ppm / K. "Difference" is to be understood as meaning in particular the difference between the CTE of the reinforcing material in the transverse direction and the CTE of the barrier material or the amount of this difference.
[0068] The difference between the CTE of the barrier material in the longitudinal direction and the CTE of the reinforcing material in the longitudinal direction is preferably in the range of 1.0 to 12.5 ppm / K, 2.5 to 10.0 ppm / K or 5.0 to 7.5 ppm / K. The difference between the CTE of the barrier material in the longitudinal direction and the CTE of the reinforcing material in the longitudinal direction may be, for example, at least 1.0 ppm / K, at least 2.5 ppm / K or at least 5.0 ppm / K. The difference between the CTE of the barrier material in the longitudinal direction and the CTE of the reinforcing material in the longitudinal direction may be, for example, at most 12.5 ppm / K, at most 10.0 ppm / K or at most 7.5 ppm / K. "Difference" is to be understood as meaning in particular the difference between the CTE of the barrier material in the longitudinal direction and the CTE of the reinforcing material in the longitudinal direction or the amount of this difference.
[0069] The composite material, in particular the composite material or the material composite of the present invention may for example contain or consist of a barrier material and a reinforcing material. The reinforcing material may in particular be selected from the group consisting of carbon fiber, silicon carbide fiber, aluminum oxide fiber, silicon oxide fiber and a combination of two or more thereof.
[0070] The composite material can be present, for example, as a material composite, in particular in the form of a layer composite. In particular, a core (for example based on a cylindrical basic shape) and a fiber braid around the core, for example a fiber braid made of carbon fibers and / or silicon carbide fibers and / or oxide fibers, can be provided. The core can also be referred to as an inner layer and can, for example, include a barrier material or consist of a barrier material.
[0071] The present invention also provides a barrier material, wherein the barrier material (i) has a higher hydrogen tightness than the plastics currently used; the barrier material (ii) is suitable for combining with fibrous reinforcement materials, especially carbon fiber structures, in terms of thermal expansion; the barrier material (iii) contributes little to the weight of the entire system and / or the barrier material (iv) has high fracture toughness.
[0072] The barrier material is in particular designed as a planar material. Planar materials are flat and therefore differ from fibers. The planar materials described here are in particular films or layers.
[0073] In particular, the barrier material of the present invention is not a fibrous material. The design of fibrous materials is associated with an increase in the hydrogen permeability, which is to be avoided according to the present invention. On the contrary, the hydrogen permeability should be low. Therefore, the barrier material is preferably not fibrous. On the contrary, a planar design of the barrier material is preferred. The barrier material is preferably layered. The barrier material is preferably a layered material or a layered material, such as a film or a layer. Therefore, the barrier material is preferably in the form of a layer, in particular a film or a layer. Preferably, the barrier layer is essentially free of pores, gaps and / or holes. Preferably, the barrier layer is a closed layer.
[0074] The barrier material of the invention preferably has a particularly high hydrogen impermeability. In other words, the hydrogen permeability of the barrier material is preferably particularly low.
[0075] The wall of the hydrogen storage according to the invention, the composite material according to the invention and / or the barrier material according to the invention preferably has a 10 logarithm of H2 permeability per mol / (m·s·Pa), in particular at a temperature of 473 K, of less than -20000, more preferably less than -20100, more preferably less than -20200, more preferably less than -20300, more preferably less than -20400, more preferably less than -20500, more preferably less than -20600, more preferably less than -20700, more preferably less than -20800, more preferably less than -20900, more preferably less than -21000, more preferably less than -21100, more preferably less than -21200, more preferably less than -21300, more preferably less than -21400, more preferably less than -21500, more preferably less than -21600, more preferably More preferably, it is less than -20,800, more preferably less than -20,900, more preferably less than -21,000, more preferably less than -21,250, more preferably less than -21,500, more preferably less than -21,750, more preferably preferably less than -22,000, more preferably less than -22,250, more preferably less than -22,500, more preferably less than -22,750, more preferably less than -23,000, more preferably less than -23,250, more preferably less than -23,500, more preferably less than -23,750, more preferably less than -24,000. The wall of the hydrogen storage according to the invention, the composite material according to the invention and / or the barrier material according to the invention, in particular at a temperature of 473 K, may have a 10-logarithm of the H2 permeability per mol / (m·s·Pa), for example, higher than -29000, higher than -28500, higher than -28000, higher than -27500, higher than -27000, higher than -26500, higher than -26000, higher than -25500, higher than -25000 or higher than -24500.
[0076] The wall of the hydrogen storage according to the invention, the composite material according to the invention and / or the barrier material according to the invention, in particular at a temperature of 473 K, can have a 10-logarithm of H2 permeability per mol / (m·s·Pa) of, for example, from greater than -29000 to less than -20000, from greater than -29000 to less than -20100, from greater than -29000 to less than -20200, from greater than -29000 to less than -20300, from greater than -29000 to less than -20400, from greater than -29000 to less than -20500, from greater than -29000 to less than -20600, from greater than -29000 to less than -20700, from greater than -29000 to less than -20800, from greater than -29000 to less than -20900, from greater than -29000 to less than -201100, from greater than -29000 to less than -201200, from greater than -29000 to less than -202400, from greater than -29000 to less than -20300, from greater than -29000 to less than -20450, from greater than -29000 to less than -20500, from greater than -29000 to less than -20670, from greater than -29000 to less than -20700, from greater than -29000 to less than -20800, from greater than -29000 to less than From greater than -29000 to less than -21000, from greater than -29000 to less than -21250, from greater than 29000 to less than -21500, from greater than -29000 to less than -21750, from greater than -28500 to less than -22000, from greater than -28000 to less than -22250, from greater than 27500 to less than -22500, from greater than -27000 to less than -22750, from greater than -26500 to less than -23000, from greater than -26000 to less than -23250, from greater than 25500 to less than -23500, from greater than -25000 to less than -23750 or from greater than -24500 to less than -24000. The H2 permeability per mol / (m·s·Pa) can be measured as described in Journal of Non-Crystalline Solids 394–395 (2014) 43–49.
[0077] The average linear coefficient of thermal expansion (CTE) of the barrier material in the range of 20° C. to 300° C. is preferably in the range of 3.5 to 9.5 ppm / K, 4.0 to 9.0 ppm / K, 4.5 to 8.5 ppm / K or 5.0 to 8.0 ppm / K. The CTE of the barrier material is preferably at least 3.5 ppm / K, at least 4.0 ppm / K, at least 4.5 ppm / K or at least 5.0 ppm / K. The CTE of the barrier material is preferably at most 9.5 ppm / K, at most 9.0 ppm / K, at most 8.5 ppm / K or at most 8.0 ppm / K. The CTE of the barrier material can in particular be calculated or determined according to ISO 7991:1998-02. The CTE of the reinforcing material can be determined according to DIN EN 16245:2013-08.
[0078] The density of the barrier material is preferably at most 2.70 g / cm 3 , more preferably at most 2.65 g / cm 3, even more preferably at most 2.60 g / cm 3 The density of the barrier material may be, for example, at least 2.20 g / cm 3 , at least 2.25g / cm 3 or at least 2.30g / cm 3 The density of the barrier material may be, for example, between 2.20 and 2.70 g / cm 3 , 2.25 to 2.65 g / cm 3 or 2.30 to 2.60 g / cm 3 within the range.
[0079] The fracture toughness of the barrier material is described by K1c, which is measured according to the method of SEPB as described in Journal of the European Ceramic Society 37 (2017) 4243-4257.
[0080] Glass is very suitable as part of the combination material of the invention, in particular as part of the material composite, in particular as a barrier material. However, the glass should have a low hydrogen permeability. Furthermore, the CTE of the glass should not differ too much from the CTE of the reinforcing material of the combination material. The use of glass as part of the combination material can allow particularly thin walls to be formed while having a sufficiently low hydrogen permeability, so that particularly light hydrogen storage devices and hydrogen tanks can be obtained, which is advantageous for tanks of any type of vehicle for reasons of energy efficiency.
[0081] Glass is also advantageous for other reasons. In particular, the material aging rate associated with hydrogen is low. In addition, composite materials, in particular material composites made of glass on the one hand and carbon fibers, silicon carbide fibers and / or oxidized fibers on the other hand, can be produced in which delamination does not occur or does not occur to a relevant extent.
[0082] In particular when used in a barrier material or as a barrier material, the glass according to the invention is preferably a planar material and therefore not fibrous. The fibrous design of the glass according to the invention is associated with an increase in the hydrogen permeability, which is to be avoided according to the invention. On the contrary, the hydrogen permeability should be low. Therefore, the glass according to the invention is preferably non-fibrous. On the contrary, a planar design of the glass according to the invention is preferred. The glass according to the invention is preferably in layered form, for example in the form of a glass layer or a glass film. Therefore, the glass according to the invention is preferably in the form of a glass layer, in particular in the form of a glass film. The use of the term "film" does not imply any restriction on the layer thickness.
[0083] The present invention relates to a glass article comprising or consisting of the glass of the present invention. The glass article of the present invention is preferably in non-fibrous form. Instead, a planar design of the glass article is preferred. The glass article is preferably designed in layers, for example in the form of a glass layer or a glass film. Therefore, the glass article is preferably in the form of a glass layer, in particular in the form of a glass film. The glass article is preferably a glass layer or a glass film.
[0084] The glass article preferably has a thickness in the range of 0.02 mm to 5.0 mm, for example 0.05 to 3.5 mm, 0.1 to 2.5 mm, 0.2 to 2.0 mm or 0.5 to 1.2 mm. The thickness of the glass article is preferably at least 0.02 mm, at least 0.05 mm, at least 0.1 mm, at least 0.2 mm or at least 0.5 mm. The thickness of the glass article is preferably at most 5.0 mm, at most 3.5 mm, at most 2.5 mm, at most 2.0 mm or at most 1.2 mm.
[0085] The difference between the maximum thickness and the minimum thickness of the glass article may also be referred to as the total thickness variation of the glass article. The total thickness variation of the glass article is preferably in the range of 0.005 mm to 1.0 mm, such as 0.01 to 0.75 mm, 0.02 to 0.5 mm or 0.05 to 0.25 mm. The total thickness variation of the glass article is preferably at least 0.005, at least 0.01 mm, at least 0.02 mm or at least 0.05 mm. The total thickness variation of the glass article is preferably at most 1.0 mm, at most 0.75 mm, at most 0.5 mm or at most 0.25 mm.
[0086] The present invention also relates to a glass comprising the following components in specified proportions (mol%):
[0087] Table 1:
[0088] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 50 75 <![CDATA[B2O3]]> 0 25 <![CDATA[Al2O3]]> 0 25 MgO 0 25 <![CDATA[Li2O]]> 0 25 <![CDATA[Na2O]]> 0 30 <![CDATA[K2O]]> 0 25 <![CDATA[ΣR2O]]> 0 30 ΣRO 0 25 <![CDATA[ΣR2O+ΣRO]]> 10 30 <![CDATA[ΣLi2O+MgO]]> 1 30
[0089] It has been found that the glass is particularly suitable as a barrier material if the content of Li2O and / or MgO is minimal. Furthermore, a minimal content of tetracoordinated boron is advantageous, but not of tricoordinated boron. Thus, with respect to the molar proportions of the respective substances, the glass according to the invention has at least as much alkali metal oxide and alkaline earth metal oxide in total as Al2O3 and B2O3, i.e. ((ΣR2O+ΣRO)≥(Al2O3+B2O3)).
[0090] This object is preferably also achieved by a targeted combination of stoichiometric glasses, which are glasses that also exist in a crystalline form with the same stoichiometry and whose properties can be assumed to be very similar for the glass and the crystal, respectively, due to the roughly identical topology of the components (as verified in many examples in the literature by NMR measurements, etc.). For this purpose, stoichiometric glasses are selected whose mixture enables the behavior that solves the problem according to the invention. In the present application, these stoichiometric glasses are also referred to as "constituent phases".
[0091] The description of glasses based on the constituent phases assigned to them is not a new concept (see, for example, EP 3473604 B1 and DE 10 2017 102 482 B4). By specifying the base glass, conclusions can be drawn about the chemical structure of the glass (see Conradt R: "Chemical structure, medium range order, and crystalline reference state of multicomponent oxide liquids and glasses", in Journal of Non-Crystalline Solids, Volumes 345-346, 15 October 2004, Pages 16-23).
[0092] Therefore, the present invention also relates to a glass having a composition characterized by the following phases constituting the glass; according to the invention, the basic system defined by the constituent phases is limited to the specified composition ranges:
[0093] Table 2:
[0094] Composition phase Minimum (Mol%) Maximum (Mol%) Silicon dioxide 0 50 Layered Sodium Silicate 0 50 Nepheline 0 100 Eucryptite 0 100 Iolite 0 100 Malinkoit 0 100 Potassium nephrite 0 40
[0095] The basic system refers explicitly to the individual constituent phases mentioned and not simply oxides.
[0096] In addition, the glass according to the present invention should satisfy additional conditions related to the components in the constituent phases or the components in the simple oxides in the formula as shown below.
[0097] Since both types of relationships (compositions given in the constituent phases and compositions given in the simple oxides) are used in parallel, a conversion matrix is first provided for the conversion of the two composition descriptions into one another.
[0098] Conversion from the components of the constituent phases to the components of the simple oxides and vice versa
[0099] For conversion purposes, the compositions of the constituent phases are given in a standardized form as follows:
[0100] Table 3:
[0101] Composition phase Chemical formula (normalized to simple oxides) Silicon dioxide <![CDATA[SiO2]]> Layered Sodium Silicate <![CDATA[(3Na2O·8SiO2) / 11]]> Iolite <![CDATA[(2MgO·2Al2O3·5SiO2) / 9]]> Malinkoit <![CDATA[(Na2O·B2O3·2SiO2) / 4]]> Eucryptite <![CDATA[(Li2O·Al2O3·2SiO2) / 4]]> Nepheline <![CDATA[(Na2O·Al2O3·2SiO2) / 4]]> Potassium nephrite <![CDATA[(K2O·Al2O3·2SiO2) / 4]]>
[0102] Convert these components to the following simple oxide combinations (expressed in Mol%):
[0103] Table 4:
[0104] # Oxide 1. <![CDATA[SiO2 <!-- 11 -->]]> 2. <![CDATA[B2O3]]> 3. <![CDATA[Al2O3]]> 4. MgO 5. <![CDATA[Li2O]]> 6. <![CDATA[Na2O]]> 7. <![CDATA[K2O]]>
[0105] This is done using the matrix given here. Here, the composition information of the base glass (in Mol%) is multiplied by the matrix from the right as a column vector:
[0106] Table 5: Matrix
[0107]
[0108] Multiplying the column vector by the matrix gives the composition of the glass in mole percent.
[0109] In contrast, compositions expressed in mole percent can be easily converted into base glass compositions by means of the respective inverse matrices. Of course, only those base glass compositions which, when converted, do not result in negative values for the base glass are considered to involve an inventive step.
[0110] Significance of the constituent phases and their selection for the purposes of the present invention
[0111] The constituent phase system described herein enables calculation of a variety of properties of the glass. These properties cannot be derived from the oxide composition alone; the requirement for specific values for these properties is a second type of restriction on the composition ranges defined in Table 2.
[0112] Compared to Table 1, the combination of Table 2 with Table 1 is itself a limitation, wherein the components in Table 1 are given as simple oxides. Within the composition space covered by Table 1, those glass compositions are useful which can be converted into the basic system of the constituent phases without negative phase fractions and which satisfy the limits on the fractions of simple oxides defined in Table 1 and the limits on the fractions of the individual constituent phases defined in Table 2 or other tables (first category limitations).
[0113] The second type of constraints consists in that the values of the coefficient of thermal expansion and / or fracture toughness and / or hydrogen permeability calculated from the components present in the constituent phases meet the requirements imposed and / or a favorable value is obtained for one or more further calculated values.
[0114] The composition is selected with respect to the constituent phases of the glass within the limits described herein. The constituent phases of the glass are of course not crystalline in the glass product, but amorphous. However, this does not mean that the constituent phases of the amorphous state have a composition that is completely different from that of the crystalline state. As described above, the topological structures of the components are comparable, i.e. the coordination of the participating cations with the surrounding oxygen atoms or the interatomic distances resulting from the coordination and bond strength between these cations and the surrounding oxygen atoms. Therefore, many properties of the glass of the present invention can be well described using the constituent phases, in particular in order to illustrate the efficiency of the present invention and the problems overcome by the present invention (see Conradt R., loc. cit.). Of course, the glass can be manufactured not only using the corresponding crystals, but also using conventional glass raw materials, as long as the stoichiometric ratio can form the corresponding basic glass composition.
[0115] The phases are selected with respect to hydrogen permeability, density and thermal expansion coefficient and fracture toughness. It is assumed that hydrogen permeability depends mainly on the packing density (the lower the packing density, the greater the hydrogen permeability) and the shear modulus G (according to the theory of Anderson and Stuart, the shear modulus is the determining factor for the activation energy when uncharged particles move in a glass matrix, see OL Anderson, DA Stuart, Calculation of Activation Energy of Ionic Conductivity, Journal of The American Ceramic Society Bd. 37, Nr. 12, Seiten 573–580, 1954).
[0116] The following gives how the density, thermal expansion coefficient, fracture toughness, bulk density and shear modulus of a given composition can be calculated from the constituent phases. These calculation methods are crucial for the selection of the constituent phases and the composition of the glass according to the invention composed of these constituent phases.
[0117] When searching for suitable calculation methods, it was surprisingly found that simple formulas for the above-mentioned properties can be found, from which characteristic values or approximate values of these properties can be calculated, so that glass compositions can be quickly classified as favorable or unfavorable glass compositions for the purposes of the present invention.
[0118] Density, Molar Volume, and Bulk Density
[0119] It is worth noting that the density ρ can be calculated from the molar mass M of the constituent phases using the lever rule. i and density ρ i It is very easy to calculate:
[0120]
[0121] The numerator of (1) is the molar mass, and the denominator is the molar volume V of the glass. mol . This means that the density of the glass systems discussed here can be predicted with an average accuracy of 1%. The density values listed in Table 6 below can be recorded in: A. Shyam, J. Muth, E. Lara-Curzio, Elastic properties of β-eucryptite in the glassy and microcracked crystalline states, Acta Materialia Volume 60, Issue 16, September 2012, Pages 5867-5876; Eucryptite, test report from the accredited testing laboratory of Schott, Mainz, Germany; Layered sodium silicate, cordierite, NHBansal, RH Doremus, Handbook of Glass Properties, Academic Press, Orlando, San Diego, New York, Austin, London, Montreal, Sydney, Tokyo, Toronto; Nephelin, OMazurin, MV Streltsina, TP Shvaiko-Shvaikovskaya, Handbook of Glass Data AC, Elsevier, Amsterdam, 1983-1987; Malinkoit, Kalsilit (Dichtewert für Kalsilit durch Extrapolation), HeraeusQuarzglas GmbH&Co.KG, Quarzstr.8, 63450 Hanau, Germany, website, (accessed September 12, 2021), Quartz_lamp_materials_EN.pdf (heraeus.com): Quarzglas.
[0122] The packing density χ of the glass is calculated from the molar volume as an intermediate parameter for further calculations. To this end, the (molar) ion volume is first calculated for each constituent phase. This refers to the volume occupied by the ions per mole of the constituent phase if they are regarded as spherical ions with what Robert Shannon calls an "effective radius" (to be precise: one mole of the constituent phase is normalized to a simple oxide), see Robert D. Shannon, Revised Effective Ionic Radii and Systematic Studies of Interatomic Distances in Halides and Chalcogenides, Acta Cryst. A32 (1976), S. 751-767. These radii vary depending on the coordination number. For cations, the necessary coordination number is taken from the mineralogical literature listed below in the discussion of the constituent phases; according to Conradt R., loc. cit., it is assumed that the coordination number of the cations in the glass is equal to the coordination number of the corresponding crystalline phase. Oxygen atoms are assigned to cations according to valence, i.e., for one sodium ion there is half an oxygen ion, etc. It was then assumed that the individual oxygen ions were coordinated to match this assignment, ie, one oxygen ion assigned to one silicon ion is bidentated, etc. If there were no explicit radius values in the table of Robert D. Shannon, loc. cit., for each coordination number, an interpolation or extrapolation was performed.
[0123] The molar ion volume and molar mass and density values obtained from it and according to
[0124]
[0125] The resulting bulk densities are listed in the table below.
[0126] Table 6: Normalized molar masses, densities and molar ionic volumes of constituent phases
[0127]
[0128] Regarding weight, the glass density calculated according to formula (1) should preferably be at most 2.70 g / cm 3 , more preferably up to 2.65 g / cm 3 , even more preferably a maximum of 2.60 g / cm 3 As density generally increases with bulk density, the glass density calculated according to formula (1) should preferably be, for example, at least 2.20 g / cm 3 , at least 2.25g / cm 3 or at least 2.30g / cm 3The glass density calculated according to formula (1) can be, for example, between 2.20 and 2.70 g / cm 3 , 2.25 to 2.65 g / cm 3 or 2.30 to 2.60 g / cm 3 within the range.
[0129] Considering that the hydrogen permeability decreases with increasing packing density, the packing density x of the glass calculated according to formula (2) may be, for example, at least 0.49, at least 0.50, at least 0.51, or at least 0.52. As the crystallization tendency generally increases with increasing packing density, the packing density x of the glass calculated according to formula (2) should preferably be, for example, at most 0.62, at most 0.61, at most 0.60, at most 0.59, at most 0.58, or at most 0.57. The packing density x of the glass calculated according to formula (2) may be, for example, in the range of 0.49 to 0.62, 0.49 to 0.61, 0.49 to 0.60, 0.50 to 0.59, 0.51 to 0.58, or 0.52 to 0.57.
[0130] Coefficient of thermal expansion
[0131] It is worth noting that the coefficient of thermal expansion (CTE) can also be calculated using a simple lever rule. To do this, the coefficient of thermal expansion CTE of the constituent phases i Its volume share and compression modulus K iWeighted and added, see the following formula (3), which is the same as the formula (12) in CP Wong, RS Bollampally, Thermal Conductivity, Elastic Modulus, and Coefficient of Thermal Expansion of Polymer Composites Filled with Ceramic Particles for Electronic Packaging, School of Materials Science and Engineering, Georgia Institute of Technology, Atlanta, Georgia 30332 (downloaded from academia.edu on September 12, 2021), (PDF) Thermal Conductivity, Elastic Modulus, and Coefficient of Thermal Expansion of Polymer Composites Filled with Ceramic Particles for Electronic Packaging | Jiao Han Guo-Academia.edu. The volume fraction of the constituent phase is directly calculated from the molar volume of the constituent phase and its molar fraction.
[0132]
[0133] CTE i From the table below:
[0134] Table 7: Normalized molar masses, densities and molar ionic volumes of constituent phases
[0135] Composition phase Chemical formula (normalized to simple oxides) <![CDATA[CTE i ]]> Silicon dioxide <![CDATA[SiO2]]> 0.6 Layered Sodium Silicate <![CDATA[(3Na2O·8SiO2) / 11]]> 13.19 Iolite <![CDATA[(2MgO·2Al2O3·5SiO2) / 9]]> 3.56 Nepheline <![CDATA[(Na2O·Al2O3·2SiO2) / 4]]> 10.8 Eucryptite <![CDATA[(Li2O·Al2O3·2SiO2) / 4]]> 7.8 Malinkoit <![CDATA[(Na2O·B2O3·2SiO2) / 4]]> 10.7 Potassium nephrite <![CDATA[(K2O·Al2O3·2SiO2) / 4]]> 11.8
[0136] Values are from: Test reports from the accredited testing laboratory of Schott, Mainz, Germany: Layered sodium silicate, cordierite, nepheline, NHBansal, RH Deremus, Handbook of Glass Properties, Academic Press, Orlando, San Diego, New York, Austin, London, Montreal, Sydney, Tokyo, Toronto; Eucryptite, Malinkoit (letzterer per extrapolation), Heraeus Quarzglas GmbH & Co. KG, Quarzstr. 8, 63450 Hanau, Germany, website, (accessed on September 12, 2021), Quartz_lamp_materials_EN.pdf (heraeus.com): Quarzglas. The values for eucryptite are obtained by extrapolating the values for eucryptite and nepheline. It is known from the literature that, for example, the thermal expansion coefficient of a metal is inversely proportional to the binding energy (or the depth of the interatomic potential well), see, for example, H. Skript zur Vorlesung, Einführung in die Materialwissenschaft I", Christian Albrechts- Kiel, S. 79-83. Thus, the CTE of eucryptite is obtained by plotting the CTE of eucryptite and nepheline versus the average bond strength (or "average potential well depth" for each cation, see explanation of elastic modulus below) versus the average binding energy for each cation and continuing the line through these points to the average binding energy for each cation.
[0137] The compression modulus K and the shear modulus G required below and therefore also given here are calculated from the elastic modulus E (see the following explanation of the calculation of the elastic modulus E according to formula (8)) and the Poisson's ratio μ (see the following explanation of the calculation of the Poisson's ratio μ according to formula (9)) according to the following:
[0138]
[0139] See for example H. Skript zur Vorlesung, Einführung in die Materialwissenschaft I", Christian Albrechts- Kiel, S. 79–83.
[0140] Since the CTE of carbon fibers in the longitudinal direction is −0.1 ppm / K and in the transverse direction is 10 ppm / K, the CTE of the glass according to the invention is preferably 3.5-9.5 ppm / K, particularly preferably 5-8 ppm / K.
[0141] The CTE of the glass calculated according to formula (3) is, for example, at least 3.5 ppm / K, at least 4.0 ppm / K, at least 4.5 ppm / K, or at least 5.0 ppm / K. The CTE of the glass calculated according to formula (3) is, for example, at most 9.5 ppm / K, at most 9.0 ppm / K, at most 8.5 ppm / K, or at most 8.0 ppm / K. The CTE of the glass calculated according to formula (3) may be, for example, in the range of 3.5 to 9.5 ppm / K, 4.0 to 9.0 ppm / K, 4.5 to 8.5 ppm / K, or 5.0 to 8.0 ppm / K.
[0142] The ratio of the coefficient of thermal expansion of the glass to the coefficient of thermal expansion of the reinforcing material is also important. The difference between the CTE of the reinforcing material and the CTE of the glass calculated according to formula (3) is preferably in the range of 0.0 to 10.0 ppm / K, 0.1 to 7.5 ppm / K, 0.2 to 5.0 ppm / K, 0.5 to 2.5 ppm / K or 1.0 to 2.0 ppm / K. The difference between the CTE of the reinforcing material and the CTE of the glass calculated according to formula (3) is preferably at most 10.0 ppm / K, at most 7.5 ppm / K, at most 5.0 ppm / K, at most 2.5 ppm / K or at most 2.0 ppm / K. The difference between the CTE of the reinforcing material and the CTE of the glass calculated according to formula (3) can be, for example, about 0.0 ppm / K, at least 0.1 ppm / K, at least 0.2 ppm / K, at least 0.5 ppm / K or at least 1.0 ppm / K. "Difference" is understood to mean in particular the difference or the amount of the difference between the CTE of the reinforcement material and the CTE of the glass calculated according to formula (3).
[0143] The difference between the CTE of the reinforcing material in the transverse direction and the CTE of the glass calculated according to formula (3) is preferably in the range of 0.0 to 10.0 ppm / K, 0.1 to 7.5 ppm / K, 0.2 to 5.0 ppm / K, 0.5 to 2.5 ppm / K, or 1.0 to 2.0 ppm / K. The difference between the CTE of the reinforcing material in the transverse direction and the CTE of the glass calculated according to formula (3) is preferably at most 10.0 ppm / K, at most 7.5 ppm / K, at most 5.0 ppm / K, at most 2.5 ppm / K, or at most 2.0 ppm / K. The difference between the CTE of the reinforcing material in the transverse direction and the CTE of the glass calculated according to formula (3) may be, for example, about 0.0 ppm / K, at least 0.1 ppm / K, at least 0.2 ppm / K, at least 0.5 ppm / K, or at least 1.0 ppm / K. “Difference” is understood in particular to mean the difference or the amount of the difference between the CTE of the reinforcing material in the transverse direction and the CTE of the glass calculated according to formula (3).
[0144] The difference between the CTE of the glass calculated according to formula (3) and the CTE of the reinforcing material in the longitudinal direction is preferably in the range of 1.0 to 12.5 ppm / K, 2.5 to 10.0 ppm / K or 5.0 to 7.5 ppm / K. The difference between the CTE of the glass calculated according to formula (3) and the CTE of the reinforcing material in the longitudinal direction can be, for example, at least 1.0 ppm / K, at least 2.5 ppm / K or at least 5.0 ppm / K. The difference between the CTE of the glass calculated according to formula (3) and the CTE of the reinforcing material in the longitudinal direction can be, for example, at most 12.5 ppm / K, at most 10.0 ppm / K or at most 7.5 ppm / K. "Difference" is to be understood as meaning in particular the difference between the CTE of the glass calculated according to formula (3) and the CTE of the reinforcing material in the longitudinal direction or the amount of the difference.
[0145] Elastic modulus
[0146] The starting point for calculating the elastic modulus is the theory of Makishima and Mackenzie, see "Direct calculation of Young's modulus of glass", "Calculation of bulk modulus, shear modulus and Poisson's ratio of glass", J. Non-Crystall. Sol., 1973 and 1975.
[0147] First we need an expression for the dissociation energy per unit volume, which can be calculated from the average bond strength and the molar volume.
[0148] In a simple picture of an oxide glass, the cations are placed in the potential wells formed by the surrounding oxygen atoms, each with a depth equal to the sum of the bond strengths of the various single bonds to the surrounding oxygen atoms, thereby concentrating the entire interaction energy with the central cation and the peripheral oxygen atoms in the potential well. It is no longer necessary to consider the reverse situation; the analysis would also be more difficult, since the oxygen atoms can be located between several different types of cations, which, in contrast, does not occur in pure oxide glasses. These values are listed in tabular form, for example in DE 10 2014 119594 A1
[0149] Table 8
[0150] cation Potential well depth / (kJ / mol) Si 1864 B 1572.5 Al 1537 Mg 999 Li 585 Na 440.5 K 395
[0151] From the glass compositions of the constituent phases specified above, the number of different cations contained in each phase, and the potential well depth for each cation listed in the table above, the average potential well depth or average bonding strength for each cation can be calculated:
[0152]
[0153] The number of cations per mole z is:
[0154]
[0155] where m is the number of cation types present, E pot,j is the potential well depth of the jth cation type listed above, z j,i is the number of cations of the jth type in the i-th constituent phase, c i (as in all formulae used herein) is the amount of substance of the i-th constituent phase.
[0156] The sum of j is shown in the following table:
[0157] Table 9
[0158]
[0159] The product of the average potential well depth per cation and the number of cations is the expected dissociation energy per mole.
[0160] As in Makishima and Mackenzie, a linear relationship between the elastic modulus and the dissociation energy density is now assumed:
[0161]
[0162] An evaluation of a range of different silicate glass types, excluding glasses with a boron content exceeding that of the alkali and alkaline earth oxides minus alumina, yields the following formula:
[0163]
[0164] You can use this (in kJ / mol), z dimensionless (number of moles of cations per mole of glass), and V mol (Unit: cm 3 ). Determine according to formula (5) and Table 9. Z is determined according to formula (6) and Table 9. V mol is the denominator in equation (1). The average error in calculating E is 2 GPa.
[0165] For hydrogen barrier materials, it is advantageous to combine low hydrogen permeability with high elastic modulus to obtain high fracture toughness, taking into account the following relationship with fracture toughness. The elastic modulus E calculated according to formula (8) can be, for example, at least 60 GPa, at least 65 GPa, at least 70 GPa, at least 75 GPa, at least 80 GPa, at least 85 GPa, or at least 90 GPa. The elastic modulus E calculated according to formula (8) can be, for example, at most 95 GPa, at most 94 GPa, at most 93 GPa, at most 92 GPa, or at most 91 GPa. The elastic modulus E calculated according to formula (8) can be, for example, in the range of 60 to 95 GPa, 65 to 94 GPa, 70 to 94 GPa, 75 to 93 GPa, 80 to 92 GPa, 85 to 92 GPa, or 90 to 91 GPa.
[0166] Poisson's ratio
[0167] Studies on a series of glasses within the scope of the invention have shown that the Poisson's ratio μ depends on the packing density, specifically to the following extent found empirically:
[0168] μ=0.5818·χ-0.0793 (9)
[0169] Calculating the Poisson's ratio according to formula (9) directly maps the above preferred range of bulk density to the corresponding Poisson's ratio range.
[0170] Hydrogen permeability
[0171] Studies on a range of glasses have shown that the hydrogen permeability p depends on the bulk density χ and the shear modulus G as described above, and more specifically to the following empirically found extent:
[0172]
[0173] The values of the specified decimal logarithms are preferably <-19500, particularly preferably <-20000, <-20100, <-20200, <-20300 or <-20400, very particularly preferably <-20500, <-20600, <-20700, <-20800 or <-20900, even more preferably <-21000 or <-21250, even more preferably <-21500 or <-21750, even more preferably <-22000 or <-22250, even more preferably <-22500 or <-22750, even more preferably <-23000 or <-23250, even more preferably <-23500 or <-23750, most preferably <-24000. The decimal logarithm of the hydrogen permeability p calculated according to formula (10) may be, for example, greater than -29000, greater than -28500, greater than -28000, greater than -27500, greater than -27000, greater than -26500, greater than -26000, greater than -25500, greater than -25000 or greater than -24500. The decimal logarithm of the hydrogen permeability p calculated according to formula (10) may be, for example, greater than -29000 to less than -20000, greater than -29000 to less than -20100, greater than -29000 to less than -20200, greater than -29000 to less than -20300, greater than -29000 to less than -20400, greater than -29000 to less than -20500, greater than -29000 to less than -20600, greater than -29000 to less than -20700, greater than -29000 to less than -20800, greater than -29000 to less than -29000, The range of the abovementioned ranges is 0 to less than 20900, greater than -29000 to less than 21750, greater than -28500 to less than -22000, greater than -28000 to less than -22250, greater than -27500 to less than -22500, greater than -27000 to less than 22750, greater than -26500 to less than -23000, greater than -26000 to less than -23250, greater than -25500 to less than -23500, greater than -25000 to less than -23750 or greater than -24500 to less than -24000.
[0174] In formula (10), G represents the shear modulus calculated according to formula (4a), and χ represents the bulk density calculated according to formula (2). In formula (10), the hydrogen permeability p specifically represents the hydrogen permeability at a temperature of 473K.
[0175] Fracture toughness K 1c
[0176] K 1cIt is understood to be a value measured according to the SEPB method. NIST has found that this value is related to the elastic modulus, see George D. Quinn, Jeffrey J. Swab, Fracture toughness of glasses as measured by the SCF and SEPB methods, Journal of the European Ceramic Society 37 (2017) 4243–4257.
[0177] K measured according to the SEPB method for a range of aluminosilicates, borosilicates, quartz glass and binary silicates in the accredited test laboratory of Schott in Mainz, Germany 1c The value is consistent with the elastic modulus value (E 计算 ) to obtain the formula:
[0178] K 1c =0.0147·E 计算 -0.3503 (11)
[0179] K calculated according to formula (11) 1c Preferably, it is at least 0.80 MPa·√m, particularly preferably at least 0.85 MPa·√m, very particularly preferably at least 0.90 MPa·√m, even more preferably at least 0.95 MPa·√m, and most preferably at least 1.00 MPa·√m. K calculated according to formula (11) 1c It may be, for example, at most 1.05 MPa·√m, at most 1.04 MPa·√m, at most 1.03 MPa·√m, at most 1.02 MPa·√m, or at most 1.01 MPa·√m. K calculated according to formula (11) 1c It may be, for example, in the range of 0.80 to 1.05 MPa·√m, 0.85 to 1.04 MPa·√m, 0.90 to 1.03 MPa·√m, 0.95 to 1.02 MPa·√m, or 1.00 to 1.01 MPa·√m.
[0180] Choose the right phase
[0181] Silicon dioxide
[0182] The lattice of SiO2 crystals is composed of three-dimensional meshes of SiO4 tetrahedrons. Quartz glass, that is, pure SiO2, also has a three-dimensional network structure, and the radius of its mesh size is about See OL Anderson, DA Stuart, Calculation of Activation Energy of Ionic Conductivity, Journal of The American Ceramic Society Bd. 37, Nr. 12, Seiten 573–580, 1954. (The mesh diameter is therefore approximately )The radius of the H2 molecule is about See OL Anderson, DA Stuart, loc. cit. In principle, quartz glass is suitable as a hydrogen barrier material.
[0183] The key values defined above for SiO2 are:
[0184]
[0185] The hydrogen permeability is significantly greater than that of the following constituent phases, which nevertheless have a high thermal expansion coefficient. SiO2 is therefore added to the glasses according to the invention primarily in order to set the thermal expansion coefficient to the desired value.
[0186] The calculated elastic modulus and fracture toughness are in the medium range.
[0187] The content of the constituent phase silicon dioxide can be, for example, in the range of 0.0 to 50 Mol%, 1.0 to 45 Mol%, 2.0 to 40 Mol%, 4.0 to 35 Mol%, 6.0 to 30 Mol%, 8.0 to 25 Mol%, or 10 to 20 Mol%. The content of the constituent phase silicon dioxide can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 4.0 Mol%, at least 6.0 Mol%, at least 8.0 Mol%, at least 10 Mol%, at least 15 Mol%, or at least 20 Mol%. The proportion of the constituent phase silicon dioxide can be, for example, at most 50 mol%, at most 45 mol%, at most 40 mol%, at most 35 mol%, at most 30 mol%, at most 25 mol%, at most 20 mol%, at most 15 mol%, at most 10 mol%, at most 5.0 mol%, at most 2.0 mol% or at most 1.0 mol%. The glass can also contain no constituent phase silicon dioxide.
[0188] Layered Sodium Silicate
[0189] Due to its higher packing density, the hydrogen permeability of layered sodium silicate (3Na2O·8SiO2) / 11 is lower than that of SiO2.
[0190] The key values defined above for (3Na2O·8SiO2) / 11 are:
[0191]
[0192]
[0193] Due to the high coefficient of thermal expansion, this constituent phase is only suitable as a mixture.
[0194] The calculated elastic modulus and fracture toughness are in the lower range.
[0195] The proportion of layered sodium silicate can be, for example, in the range of 0.0 to 50 Mol%, 1.0 to 45 Mol%, 2.0 to 40 Mol%, 5.0 to 35 Mol%, 10 to 30 Mol%, 20 to 25 Mol%. The proportion of layered sodium silicate can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 10 Mol%, at least 15 Mol%, at least 20 Mol%, at least 25 Mol% or at least 30 Mol%. The proportion of layered sodium silicate can be, for example, at most 50 Mol%, at most 45 Mol%, at most 40 Mol%, at most 35 Mol%, at most 30 Mol%, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 10 Mol%, at most 8.0 Mol%, at most 6.0 Mol%, at most 5.0 Mol%, at most 4.0 Mol%, at most 2.0 Mol% or at most 1.0 Mol%. The glass can also be free of layered sodium silicate.
[0196] Nepheline
[0197] In order to achieve a higher hydrogen barrier function than SiO2, a so-called "packed structure" can be converted. This is a crystal or glass whose basic structure is the same as SiO2, a three-dimensional tetrahedral network, but in which alkali metal or alkaline earth metal ions are embedded in the network, which firstly additionally hinder the transport of hydrogen and secondly represent a diffusion hardening, i.e. an increase in the elastic modulus. A suitable system is nepheline, which consists of a three-dimensional network of SiO4 and AlO4 tetrahedra, into which sodium ions are built. According to the invention, one mole of nepheline is understood to mean one mole of (Na2O·Al2O3·2SiO2) / 4.
[0198] The key values defined above for nepheline are:
[0199]
[0200]
[0201] In view of the above values, nepheline is suitable as the "base phase" of the hydrogen barrier glass, to which, however, SiO2, for example, must be added in order to take thermal expansion into account.
[0202] The calculated elastic modulus and fracture toughness are in the medium range.
[0203] The content of nepheline can be, for example, in the range of 0.0 to 100 Mol%, 1.0 to 90 Mol%, 2.0 to 80 Mol%, 5.0 to 70 Mol%, 10 to 60 Mol%, 20 Mol% to 50 Mol% or 30 to 40 Mol%. The content of nepheline can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 10 Mol%, at least 15 Mol%, at least 20 Mol%, at least 25 Mol% or at least 30 Mol%. The proportion of nepheline can be, for example, at most 90 Mol%, at most 80 Mol%, at most 70 Mol%, at most 60 Mol%, at most 50 Mol%, at most 40 Mol%, at most 35 Mol%, at most 30 Mol%, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 10 Mol%, at most 5.0 Mol%, at most 2.0 Mol% or at most 1.0 Mol%. The glass can also be free of nepheline.
[0204] Eucryptite
[0205] Compared to nepheline, the E modulus of eucryptite is significantly increased, which in turn leads to a lower hydrogen permeability. According to the present invention, one mole of eucryptite is understood to be one mole of (Li2O·Al2O3·2SiO2) / 4.
[0206] The key values defined above for eucryptite are:
[0207]
[0208] In view of these values, eucryptite is even more suitable than nepheline as a base phase for hydrogen barrier materials. Due to the smaller expansion coefficient, the amount of SiO2 added can be lower in order to obtain an expansion coefficient comparable to the average expansion coefficient of carbon fibers. This in turn favors the hydrogen barrier effect. The calculated elastic modulus and fracture toughness are in the upper range. The disadvantage is the price of the lithium oxide component.
[0209] The content of eucryptite can be, for example, in the range of 0.0 to 100 Mol%, 1.0 to 90 Mol%, 2.0 to 80 Mol%, 5.0 to 70 Mol%, 10 to 60 Mol%, 20 Mol% to 50 Mol% or 30 to 40 Mol%. The content of eucryptite can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 10 Mol%, at least 15 Mol%, at least 20 Mol%, at least 25 Mol%, at least 30 Mol%, at least 40 Mol%, at least 50 Mol% or at least 60 Mol%. The proportion of eucryptite can be, for example, at most 90 Mol%, at most 80 Mol%, at most 70 Mol%, at most 60 Mol%, at most 50 Mol%, at most 40 Mol%, at most 35 Mol%, at most 30 Mol%, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 10 Mol%, at most 5.0 Mol%, at most 2.0 Mol% or at most 1.0 Mol%. The glass can also be free of eucryptite.
[0210] Iolite
[0211] According to the invention, one mole of cordierite is understood to be one mole of (2MgO·2Al2O3·5SiO2) / 9.
[0212] The key values defined above for cordierite are:
[0213]
[0214] Due to its low expansion coefficient and low hydrogen permeability, cordierite is an excellent base phase for hydrogen barrier materials. In order to achieve the required expansion coefficient, constituent phases such as nepheline or eucryptite must be added, which are very good barrier materials themselves.
[0215] The calculated elastic modulus and fracture toughness are in the higher range.
[0216] The proportion of cordierite can be, for example, in the range of 0.0 to 100 Mol%, 1.0 to 90 Mol%, 2.0 to 80 Mol%, 5.0 to 70 Mol%, 10 to 60 Mol%, 20 Mol% to 50 Mol% or 30 to 40 Mol%. The proportion of cordierite can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 10 Mol%, at least 15 Mol%, at least 20 Mol%, at least 25 Mol%, at least 30 Mol%, at least 40 Mol%, at least 50 Mol% or at least 60 Mol%. The proportion of cordierite can be, for example, at most 90 Mol%, at most 80 Mol%, at most 75 Mol%, at most 70 Mol%, at most 60 Mol%, at most 50 Mol%, at most 40 Mol%, at most 35 Mol%, at most 30 Mol%, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 10 Mol%, at most 5.0 Mol%, at most 2.0 Mol% or at most 1.0 Mol%. The glass can also be cordierite-free.
[0217] Malinkoit
[0218] According to the invention, one mole of Malinkoit is understood to mean one mole of (Na2O·B2O3·2SiO2) / 4.
[0219] The key values defined above for Malinkoit are:
[0220]
[0221] Due to its very low hydrogen permeability, Malinkoite is an excellent additional component for hydrogen barrier materials. However, in order to achieve the required expansion coefficient, a base glass such as cordierite must be used.
[0222] Compared to its aluminum analogue, nepheline, Malinkoit has a very low hydrogen permeability. Analogous systems with tetrahedrally coordinated boron or aluminum, respectively, are characterized by stiffer bond angles, shorter bond distances and lower compressibility of the boron-containing analogues than the aluminum-containing analogues. All these differences have an inhibitory effect on hydrogen diffusion. Therefore, from this point of view, Malinkoit is a particularly preferred constituent phase.
[0223] The calculated elastic modulus and fracture toughness are in the higher range.
[0224] The share of Malinkoit can be, for example, in the range of 0.0 to 100 Mol%, 1.0 to 90 Mol%, 2.0 to 80 Mol%, 5.0 to 70 Mol%, 10 to 60 Mol%, 20 Mol% to 50 Mol%, or 30 to 40 Mol%. The share of Malinkoit can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 10 Mol%, at least 15 Mol%, at least 20 Mol%, at least 25 Mol%, at least 30 Mol%, at least 40 Mol%, at least 50 Mol%, or at least 60 Mol%. The proportion of Malinkoit can be, for example, at most 90 Mol%, at most 80 Mol%, at most 75 Mol%, at most 70 Mol%, at most 60 Mol%, at most 50 Mol%, at most 40 Mol%, at most 35 Mol%, at most 30 Mol%, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 10 Mol%, at most 5.0 Mol%, at most 2.0 Mol% or at most 1.0 Mol%. The glass can also be free of Malinkoit.
[0225] Coralite and Malinkoit
[0226] The sum of the molar fractions of cordierite and Malinkoite and the ratio of the molar fraction of cordierite to the molar fraction of Malinkoite are also particularly important. Cordierite and Malinkoite are constituent phases that combine a high elastic modulus and high fracture toughness with very low hydrogen permeability. Therefore, their sum preferably accounts for a large proportion.
[0227] The sum of the molar fractions of cordierite and Malinkoit is preferably in the range of 50 to 100 Mol%, for example, 60 to 90 Mol% or 70 to 80 Mol%. The sum of the molar fractions of cordierite and Malinkoit is preferably at least 50 Mol%, for example, at least 60 Mol% or at least 70 Mol%. The sum of the molar fractions of cordierite and Malinkoit can be, for example, at most 90 Mol% or at most 80 Mol%.
[0228] The molar fraction of cordierite is preferably at least as large as the molar fraction of Malinkoit. The molar fraction of cordierite is preferably greater than the molar fraction of Malinkoit. The difference between the molar fraction of cordierite and the molar fraction of Malinkoit is preferably in the range of 0 to 40 Mol%, for example, in the range of 10 to 30 Mol%. The molar fraction of cordierite can exceed the molar fraction of Malinkoit, for example, by at least 10 Mol% or at least 20 Mol%. The ratio of the molar fraction of cordierite to the molar fraction of Malinkoit is preferably in the range of 0.5 to 5.0, preferably 1.0 to 4.0, 1.3 to 3.0, 1.5 to 2.5 or 1.6 to 2.0. The ratio of the molar fraction of cordierite to the molar fraction of Malinkoit is preferably at least 0.5, more preferably at least 1.0, for example, at least 1.3, at least 1.5 or at least 1.6. The ratio of the molar fraction of cordierite to the molar fraction of Malinkoit is preferably at most 5.0, more preferably at most 4.0, for example at most 3.0, at most 2.5 or at most 2.0. Since cordierite has a thermal expansion coefficient of 3.56 ppm / K and Malinkoit has a thermal expansion coefficient of 10.7 ppm / K, the ratio of the molar fractions is particularly preferably used to adapt the thermal expansion coefficient of the barrier material to the thermal expansion coefficient of the reinforcing material, in particular the average thermal expansion coefficient of the carbon fibers.
[0229] Potassium nephrite
[0230] According to the present invention, one mole of pyroxene is understood to be one mole of (K2O·Al2O3·2SiO2) / 4.
[0231] The key values defined above for pyroxene are:
[0232]
[0233]
[0234] Due to its low hydrogen permeability, pyroxene is a good base glass mixture for hydrogen barrier materials. At the same time, the low elastic modulus distinguishes pyroxene from all other constituent phases with very low hydrogen permeabilities, which is advantageous for the flexibility of the subsequent components. Taking thermal expansion into account, SiO2 can also be added, for example. Like all aluminosilicate glasses, it is also a low-brittle glass. The calculated elastic modulus and fracture toughness are in the lower range.
[0235] The proportion of pyroxene can be, for example, in the range of 0.0 to 40 Mol%, 1.0 to 35 Mol%, 2.0 to 30 Mol%, 5.0 to 25 Mol% or 10 to 20 Mol%. The proportion of pyroxene can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 10 Mol%, at least 15 Mol% or at least 20 Mol%. The proportion of pyroxene can be, for example, at most 40 Mol%, at most 35 Mol%, at most 30 Mol%, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 10 Mol%, at most 5.0 Mol%, at most 2.0 Mol% or at most 1.0 Mol%. The glass can also be free of pyroxene.
[0236] Other components
[0237] In addition to the components already mentioned, the glass may also contain further components, which are referred to herein as "residues". The fraction of residues in the glass according to the invention is preferably a maximum of 3.0 mol%, so as not to interfere with the glass properties set by careful selection of a suitable base glass. In particular, the content of individual oxides is preferably limited to <0.5 mol%. In a particularly preferred embodiment, the fraction of residues in the glass is at most 2.0 mol%, more preferably at most 1.0 mol% or at most 0.5 mol%. The residues especially include oxides that are not included in the base glass mentioned herein. Thus, the residues are particularly free of SiO2, Al2O3, B2O3, Na2O, Li2O, K2O, MgO. In some embodiments, the glass is free of residues, which means that the glass essentially contains only oxides of the constituent phases of the phase system described herein to which it is assigned.
[0238] When it is stated in this specification that the glass does not contain a certain component or constituent phase or does not contain a certain component or constituent phase, this means that the component or constituent phase may only be present in the glass as an impurity. This means that its addition amount is not large. According to the present invention, the non-essential amount is less than 5000 ppm (molar, relative to oxide), preferably less than 4000 ppm (molar, relative to oxide), more preferably less than 3000 ppm (molar, relative to oxide), more preferably less than 2000 ppm (molar, relative to oxide), more preferably less than 1000 ppm (molar, relative to oxide), preferably less than 500 ppm (molar, relative to oxide), preferably less than less than 300 ppm (molar, relative to oxide), particularly preferably less than 100 ppm (molar, relative to oxide), most preferably less than 50 ppm (molar, relative to oxide), most preferably less than 10 ppm (molar, relative to oxide). The glass of the present invention is particularly free of uranium, lead, arsenic, antimony, bismuth and / or cadmium.
[0239] Residues do not appear in the formula. All calculations are performed on the basis that the proportion of the constituent phases is 100%.
[0240] The difference between trigonal boron and tetracoordinate boron
[0241] Taking into account the proportion limits specified in said table, all glasses according to the invention can be represented by a combination of the constituent phases listed in Table 2. Glasses which do not allow this do not belong to the invention. These glasses include in particular all glasses which are identical to the glasses according to the invention, which have corresponding proportions of the oxides SiO2, B2O3, Al2O3, Li2O, Na2O, K2O and / or MgO, but have an excess of boron.
[0242] The glass according to the invention does not contain excess boron. In particular, the glass according to the invention is suitable for the following:
[0243] (ΣR2O+ΣRO)≥(Al2O3+B2O3)(12a)
[0244] According to the invention, ΣRO+ΣRO is to be understood as the sum of the proportions of alkali metal oxides and alkaline earth metal oxides, in particular the sum of the proportions of LiO, NaO, KO, MgO, CaO, SrO and BaO. The glass according to the invention preferably has only a small proportion of CaO, SrO and BaO or even contains no CaO, SrO and / or BaO. These oxides are not present in the constituent phase according to the invention and therefore belong to the above-mentioned residues, whose proportion is preferably small. Therefore, in a preferred embodiment, (12a) can be simplified as follows:
[0245] (Li2O+Na2O+K2O+MgO)≥(Al2O3+B2O3)(12b)
[0246] In inequalities (12a, b), the chemical formula of the individual simple oxides represents their molar fraction in the corresponding glass. Glasses to which inequalities (12a) and / or inequalities (12b) apply are characterized in that the oxygen provided by the alkali metal and alkaline earth metal oxides is transferred primarily to the aluminum atoms present so that they can achieve the above-mentioned four-fold coordination, see, for example, S. Bruns, T. Uesbeck, D. Weil, D. L. van Wüllen, K. Durst, D. de Ligny, Influence of Al2O3 Addition on Structure and Mechanical Properties of Borosilicate Glasses, Front. Mater. 7: 189 (2020). The remaining oxygen provided by the alkali metal and alkaline earth metal oxides is used to make the boron atoms achieve tetracoordination. Considering the excess alkali metal and alkaline earth metal oxides, there is no remaining boron, and due to the lack of additional oxygen, boron can only enter trigonal coordination. Therefore, the glass of the present invention preferably contains tetracoordinated boron, but in particular does not contain trigonal boron.
[0247] Triangular boron is not good for barrier materials. This is because triangular boron tends to aggregate into larger planar structures, i.e., borane rings. Diffusion paths that increase hydrogen permeability appear in parallel with these borane rings. This is also reflected in the measurements. See also the literature values for borosilicates, aluminosilicates, and dibasic silicates published by Welter et al. in T. Welter, R. Müller J. Deubener, U. Marzok, and S. Reinsch, Hydrogen Permeation Through Glass, Front. Mater. 6: 342 (2020). Borosilicates are barium borosilicate glasses denoted by "BABS" studied by Ried et al. in P. Ried, M. Gaber, R. Müller, J. Deubener, Hydrogen permeability of a barium-aluminoborosilicate glass - A methodical approach, Journal of Non-Crystalline Solids 394-395 (2014), 43-49, and borosilicate glasses denoted by "BS3" studied by the same authors in the same publication, as well as the systematic Corning codes 3320, 7040, 7052, 7720, 7740 and 7900 considered by Shelby in James E. Shelby, Handbook of Diffusion in Solids and Melts, ASM International, Chicago, IL (1996). In all these glasses, the sum of the mass fractions of B2O3 and Al2O3 is greater than the sum of the mass fractions of the alkali metal oxide R2O and the alkaline earth metal oxide RO. Therefore, no glass satisfies inequality (12a).
[0248] They are therefore not in accordance with the invention and also have a relatively high hydrogen permeability. The hydrogen permeability of the borosilicate glasses considered by Ried and Shelby (which can be found in Welter et al.) is higher than the hydrogen permeabilities of the aluminosilicate and binary silicate glasses considered by Welter et al. An analysis of the components according to inequalities (12a, b) leads to the conclusion that the hydrogen permeability-reducing effect of the packing structure present in the examples of Ried and Shelby is overcompensated by the hydrogen permeability-increasing effect of the largely trigonally coordinated boron.
[0249] Preferred glass composition
[0250] Preferred embodiments result from the above basic system by specifying the desired thermal expansion, density and bulk density or the desired ranges of the mentioned parameters.
[0251] The glass preferably has the following oxide composition characteristics:
[0252]
[0253]
[0254] The content of SiO2 can be, for example, at least 50 mol%, at least 51 mol%, at least 52 mol%, at least 55 mol% or at least 57 mol%. The content of SiO2 can be, for example, at most 75 mol%, at most 70 mol%, at most 68 mol%, at most 65 mol%, at most 64 mol% or at most 63 mol%. The content of SiO2 can be, for example, in the range of 50 to 75 mol%, 50 to 70 mol%, 51 to 68 mol%, 52 to 65 mol%, 55 to 64 mol% or 57 to 63 mol%.
[0255] The content of B2O3 can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 3.0 Mol%, at least 4.0 Mol% or at least 5.0 Mol%. The content of B2O3 can be, for example, at most 25 Mol%, at most 20 Mol%, at most 18 Mol%, at most 15 Mol%, at most 13 Mol% or at most 11 Mol%. The content of B2O3 can be, for example, in the range of 0.0 to 25 Mol%, 0.0 to 20 Mol%, 1.0 to 18 Mol%, 2.0 to 15 Mol%, 4.0 to 13 Mol% or 5.0 to 11 Mol%.
[0256] The content of Al2O3 can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 10 Mol%, at least 11 Mol%, at least 12 Mol%, at least 13 Mol%, or at least 14 Mol%. The content of Al2O3 can be, for example, at most 25 Mol%, at most 24 Mol%, at most 23 Mol%, at most 22 Mol%, at most 21 Mol%, at most 20 Mol%, at most 19 Mol%, at most 18 Mol%, or at most 17 Mol%. The proportion of Al2O3 can be, for example, in the range of 0.0 to 25 Mol%, 1.0 to 24 Mol%, 2.0 to 23 Mol%, 5.0 to 22 Mol%, 10 to 21 Mol%, 11 Mol% to 20 Mol%, 12 to 19 Mol%, 13 to 18 Mol% or 14 to 17 Mol%.
[0257] The sum of the proportions of B2O3 and Al2O3 may be, for example, at least 5.0 Mol%, at least 8.0 Mol%, at least 10 Mol%, at least 15 Mol% or at least 17 Mol%. The sum of the proportions of B2O3 and Al2O3 may be, for example, at most 30 Mol%, at most 28 Mol%, at most 26 Mol%, at most 25 Mol% or at most 24 Mol%. The sum of the proportions of B2O3 and Al2O3 may be, for example, in the range of 5.0 to 30 Mol%, 8.0 to 28 Mol%, 10 to 26 Mol%, 15 to 25 Mol% or 17 to 24 Mol%.
[0258] The content of MgO can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 3.0 Mol%, at least 4.0 Mol%, at least 5.0 Mol%, at least 6.0 Mol%, at least 7.0 Mol% or at least 8.0 Mol%. The content of MgO can be, for example, at most 30 Mol%, at most 25 Mol%, at most 23 Mol%, at most 20 Mol%, at most 18 Mol%, at most 15 Mol%, at most 14 Mol%, at most 12 Mol% or at most 10 Mol%. The proportion of MgO can be, for example, in the range of 0.0 to 30 Mol%, 1.0 to 25 Mol%, 2.0 to 23 Mol%, 3.0 to 20 Mol%, 4.0 to 18 Mol%, 5.0 Mol% to 15 Mol%, 6.0 to 14 Mol%, 7.0 to 12 Mol% or 8.0 to 10 Mol%. MgO has been found to be particularly advantageous for achieving low hydrogen permeability.
[0259] The content of Li2O can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 10 Mol%, at least 15 Mol%, or at least 20 Mol%. The content of Li2O can be, for example, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 10 Mol%, or at most 5.0 Mol%. The content of Li2O can be, for example, in the range of 0.0 to 25 Mol%, 0.0 to 20 Mol%, 0.0 to 15 Mol%, 1.0 to 10 Mol%, or 2.0 to 5.0 Mol%.
[0260] The proportion of Na2O can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 4.0 Mol%, at least 5.0 Mol% or at least 7.0 Mol%. The proportion of Na2O can be, for example, at most 30 Mol%, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 15 Mol%, at most 14 Mol%, at most 13 Mol%, at most 12 Mol% or at most 11 Mol%. The proportion of Na2O can be, for example, in the range of 0.0 to 30 Mol%, 0.0 to 25 Mol%, 0.0 to 20 Mol%, 0.0 to 15 Mol%, 1.0 to 14 Mol%, 2.0 Mol% to 13 Mol%, 4.0 to 12 Mol% or 5.0 to 11 Mol%.
[0261] The proportion of KO can be, for example, at least 1.0 Mol%, at least 2.0 Mol%, at least 3.0 Mol%, at least 4.0 Mol% or at least 5.0 Mol%. The proportion of KO can be, for example, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 12 Mol%, at most 10 Mol%, at most 8.0 Mol% or at most 6.0 Mol%. The proportion of KO can be, for example, in the range of 0.0 to 25 Mol%, 0.0 to 20 Mol%, 0.0 to 15 Mol%, 0.0 to 12 Mol%, 0.0 to 10 Mol%, 0.0 Mol% to 8.0 Mol% or 0.0 to 6.0 Mol%.
[0262] According to the invention, ΣR2O is understood to be the sum of the proportions of alkali metal oxides, in particular the sum of the proportions of Li2O, Na2O and K2O. ΣR2O can, for example, be at least 1.0 Mol%, at least 2.0 Mol%, at least 4.0 Mol%, at least 5.0 Mol% or at least 6.0 Mol%. For example, ΣR2O can be at most 30 Mol%, at most 25 Mol%, at most 22 Mol%, at most 20 Mol%, at most 18 Mol% or at most 17 Mol%. For example, ΣR2O can be in the range of 0.0 to 30 Mol%, 0.0 to 25 Mol%, 1.0 to 22 Mol%, 2.0 to 20 Mol%, 4.0 to 18 Mol% or 5.0 to 17 Mol%.
[0263] According to the invention, ΣRO is understood to mean the sum of the proportions of alkaline earth metal oxides, in particular the sum of the proportions of MgO, CaO, SrO and BaO. For example, ΣRO may be at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, at least 6.0 Mol% or at least 8.0 Mol%. For example, ΣRO may be at most 25 Mol%, at most 20 Mol%, at most 18 Mol%, at most 15 Mol% or at most 14 Mol%. For example, ΣRO may be in the range of 0.0 to 25 Mol%, 2.0 to 20 Mol%, 5.0 to 18 Mol%, 6.0 to 15 Mol% or 8.0 to 14 Mol%.
[0264] According to the invention, ΣRO+ΣRO is understood to be the sum of the proportions of alkali metal oxides and alkaline earth metal oxides, in particular the sum of the proportions of LiO, NaO, KO, MgO, CaO, SrO and BaO. For example, ΣRO+ΣRO may be at least 5.0 mol%, at least 8.0 mol%, at least 10 mol%, at least 12 mol%, at least 15 mol% or at least 17 mol%. For example, ΣRO+ΣRO may be at most 30 mol%, at most 28 mol%, at most 27 mol%, at most 26 mol%, at most 25 mol% or at most 24 mol%. ΣRO+ΣRO may be, for example, in the range of 5.0 to 30 mol%, 8.0 to 28 mol%, 10 to 27 mol%, 12 to 26 mol%, 15 to 25 mol% or 17 to 24 mol%.
[0265] The ratio of the substance amount fractions of ΣR2O+ΣRO and the sum of B2O3+Al2O3, i.e. the fraction ratio (ΣR2O+ΣRO) / (B2O3+Al2O3), may be particularly important. Advantageously, the substance amount fraction of the sum of ΣR2O+ΣRO is similar to or even identical to the substance amount fraction of the sum of B2O3+Al2O3, so that the fraction ratio (ΣR2O+ΣRO) / (B2O3+Al2O3) is close to or equal to 1:1. If the fraction ratio is too high, there are too many non-bridging oxygen atoms (NBO), which has a negative impact on chemical resistance. Preferably, the fraction ratio (ΣR2O+ΣRO) / (B2O3+Al2O3) is at least 1.00:1.00. If the ratio is too small, there is too much triangular boron (which has a negative impact on the desired hydrogen barrier effect) or the system will devitrify in the absence of boron. The proportion ratio (ΣR2O+ΣRO) / (B2O3+Al2O3) can be, for example, 1.00:1 to 1.25:1, 1.00:1 to 1.20:1, 1.00:1 to 1.15:1, 1.00:1 to 1.10:1, 1.00:1 to 1.05:1, 1.00:1 to 1.02:1 or 1.00:1 to 1.01:1 or 1:1, for example about 1.00:1.00. The proportion ratio (ΣR2O+ΣRO) / (B2O3+Al2O3) is at least about 1.00:1.00. For example, the proportion ratio (ΣR2O+ΣRO) / (B2O3+Al2O3) can be at most 1.25:1, at most 1.20:1, at most 1.15:1, at most 1.10:1, at most 1.05:1, at most 1.02:1, at most 1.01:1 or at most 1:1, for example at most about 1.00:1.00.
[0266] The difference in the amount fractions of the sum of ΣR2O+ΣRO and the sum of B2O3+Al2O3, i.e. (ΣR2O+ΣRO)-(B2O3+Al2O3), can be particularly important. Advantageously, the amount fraction of the sum of ΣR2O+ΣRO is similar to or even identical to the amount fraction of the sum of B2O3+Al2O3, so that the difference (ΣR2O+ΣRO)-(B2O3+Al2O3) is close to or equal to 0. If a large excess of alkali metals and alkaline earth metals is present, there are too many non-bridging oxygen atoms (non-bridging oxygen (NBO)). If B2O3 and Al2O3 are in excess, there is too much triangular boron. Triangular boron has a negative impact on the desired hydrogen barrier effect. In particular, an excess of B2O3+Al2O3 should therefore be avoided. Preferably, the difference (ΣR2O+ΣRO)-(B2O3+Al2O3) ≥ 0 Mol%.
[0267] The sum of the contents of Li2O and MgO is also particularly important. The sum of the contents of Li2O and MgO may, for example, be in the range of 1.0 to 30 Mol%, 2.0 to 25 Mol%, 5.0 to 20 Mol%, or 10 to 15 Mol%. The sum of the contents of Li2O and MgO may, for example, be at least 1.0 Mol%, at least 2.0 Mol%, at least 5.0 Mol%, or at least 10 Mol%, in some embodiments even at least 15 Mol%, or at least 20 Mol%. The sum of the contents of Li2O and MgO may, for example, be at most 30 Mol%, at most 25 Mol%, or at most 20 Mol%, in some embodiments even at most 15 Mol%, or at most 10 Mol%.
[0268] The proportion of MgO is preferably greater than the proportion of Li2O. The use of MgO can achieve particularly low hydrogen permeability. The proportion of MgO is preferably at least 1.0 Mol%, more preferably at least 2.0 Mol%, further preferably at least 3.0 Mol%, further preferably at least 4.0 Mol%, more preferably at least 5.0 Mol%, further preferably at least 6.0 Mol%. The proportion of MgO can be, for example, at most 30 Mol%, at most 25 Mol%, at most 20 Mol%, at most 15 Mol%, at most 12 Mol%, or at most 10 Mol% greater than the proportion of Li2O. The difference between the proportions of MgO and Li2O can be, for example, in the range of 1.0 to 30 Mol%, 2.0 to 25 Mol%, 3.0 to 20 Mol%, 4.0 to 15 Mol%, 5.0 to 12 Mol%, or 6.0 to 10 Mol%.
[0269] Preferred compositions are characterized by the following composition ranges:
[0270] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 50 70 <![CDATA[B2O3]]> 0 20 <![CDATA[Al2O3]]> 10 25 MgO 0 25 <![CDATA[Li2O]]> 0 25 <![CDATA[Na2O]]> 0 15 <![CDATA[K2O]]> 0 15 <![CDATA[ΣR2O]]> 0 25 ΣRO 0 25 <![CDATA[ΣR2O+ΣRO]]> 10 30
[0271] Another preferred composition is characterized by the following composition ranges:
[0272] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 51 68 <![CDATA[B2O3]]> 1 18 <![CDATA[Al2O3]]> 11 22 MgO 2 20 <![CDATA[Li2O]]> 0 20 <![CDATA[Na2O]]> 1 14 <![CDATA[K2O]]> 0 12 <![CDATA[ΣR2O]]> 1 22 ΣRO 2 20 <![CDATA[ΣR2O+ΣRO]]> 10 28
[0273] Another preferred composition is characterized by the following constituent glass phases:
[0274] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 52 65 <![CDATA[B2O3]]> 2 15 <![CDATA[Al2O3]]> 12 20 MgO 5 18 <![CDATA[Li2O]]> 0 15 <![CDATA[Na2O]]> 2 13 <![CDATA[K2O]]> 0 10 <![CDATA[ΣR2O]]> 2 20 ΣRO 5 18 <![CDATA[ΣR2O+ΣRO]]> 10 26
[0275] Another preferred composition is characterized by the following composition ranges:
[0276]
[0277]
[0278] Another preferred composition is characterized by the following composition ranges:
[0279] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 57 63 <![CDATA[B2O3]]> 5 11 <![CDATA[Al2O3]]> 14 17 MgO 8 14 <![CDATA[Li2O]]> 0 5 <![CDATA[Na2O]]> 5 11 <![CDATA[K2O]]> 0 6 <![CDATA[ΣR2O]]> 5 17 ΣRO 8 14 <![CDATA[ΣR2O+ΣRO]]> 17 24
[0280] Another preferred composition is characterized by the following composition ranges:
[0281]
[0282]
[0283] Another preferred composition is characterized by the following composition ranges:
[0284] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 50 68 <![CDATA[B2O3]]> 2 18 <![CDATA[Al2O3]]> 2 22 MgO 2 18 <![CDATA[Li2O]]> 0 10 <![CDATA[Na2O]]> 2 20 <![CDATA[K2O]]> 0 15 <![CDATA[ΣR2O]]> 4 22 ΣRO 2 18 <![CDATA[ΣR2O+ΣRO]]> 15 27 <![CDATA[ΣLi2O+MgO]]> 5 20
[0285] Another preferred composition is characterized by the following composition ranges:
[0286]
[0287]
[0288] Preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0289]
[0290] More preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0291]
[0292] More preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0293]
[0294]
[0295] More preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0296]
[0297] More preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0298]
[0299] More preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0300]
[0301] More preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0302]
[0303] More preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0304]
[0305] More preferably, the composition of the glass of the present invention is characterized by the following constituent phases constituting the glass:
[0306]
[0307] Preferably, the present invention relates to a glass comprising the following components expressed in the specified proportions (in mol %):
[0308] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 50 75 <![CDATA[B2O3]]> 0 25 <![CDATA[Al2O3]]> 0 25 MgO 0 25 <![CDATA[Li2O]]> 0 25 <![CDATA[Na2O]]> 0 30 <![CDATA[K2O]]> 0 25 <![CDATA[ΣR2O]]> 0 30 ΣRO 0 25 <![CDATA[ΣR2O+ΣRO]]> 10 30 <![CDATA[ΣLi2O+MgO]]> 1 30
[0309] The sum of the molar proportions of the alkali metal oxide R2O and the alkaline earth metal oxide RO is equal to or greater than the sum of the molar proportions of B2O3 and Al2O3, and the composition of the glass is also characterized by the following constituent phases constituting the glass:
[0310]
[0311]
[0312] And wherein the decimal logarithm of the hydrogen permeability p calculated according to formula (10) is less than -20000.
[0313] The present invention particularly preferably relates to a glass containing the components expressed in the specified proportions (in mol %):
[0314] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 50 70 <![CDATA[B2O3]]> 1 20 <![CDATA[Al2O3]]> 1 24 MgO 1 20 <![CDATA[Li2O]]> 0 15 <![CDATA[Na2O]]> 1 25 <![CDATA[K2O]]> 0 20 <![CDATA[ΣR2O]]> 1 25 ΣRO 1 20 <![CDATA[ΣR2O+ΣRO]]> 12 28 <![CDATA[ΣLi2O+MgO]]> 2 25
[0315] The sum of the molar proportions of the alkali metal oxide R2O and the alkaline earth metal oxide RO is equal to or greater than the sum of the molar proportions of B2O3 and Al2O3, and the composition of the glass is also characterized by the following constituent phases constituting the glass:
[0316]
[0317]
[0318] And wherein the decimal logarithm of the hydrogen permeability p calculated according to formula (10) is less than -20500.
[0319] The present invention also preferably relates to a glass comprising the following components expressed in the specified proportions (in mol%):
[0320] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 50 68 <![CDATA[B2O3]]> 2 18 <![CDATA[Al2O3]]> 2 22 MgO 2 18 <![CDATA[Li2O]]> 0 10 <![CDATA[Na2O]]> 2 20 <![CDATA[K2O]]> 0 15 <![CDATA[ΣR2O]]> 4 22 ΣRO 2 18 <![CDATA[ΣR2O+ΣRO]]> 15 27 <![CDATA[ΣLi2O+MgO]]> 5 20
[0321] The sum of the molar proportions of the alkali metal oxide R2O and the alkaline earth metal oxide RO is equal to or greater than the sum of the molar proportions of B2O3 and Al2O3, and the composition of the glass is also characterized by the following constituent phases constituting the glass:
[0322]
[0323]
[0324] And wherein the decimal logarithm of the hydrogen permeability p calculated according to formula (10) is less than -21000.
[0325] The present invention also more preferably relates to a glass comprising the following components in specified proportions (in mol%):
[0326] Minimum (Mol%) Maximum (Mol%) <![CDATA[SiO2]]> 50 65 <![CDATA[B2O3]]> 3 15 <![CDATA[Al2O3]]> 5 20 MgO 4 18 <![CDATA[Li2O]]> 0 5 <![CDATA[Na2O]]> 4 15 <![CDATA[K2O]]> 0 12 <![CDATA[ΣR2O]]> 5 20 ΣRO 4 18 <![CDATA[ΣR2O+ΣRO]]> 17 26 <![CDATA[ΣLi2O+MgO]]> 5 20
[0327] The sum of the molar proportions of the alkali metal oxide R2O and the alkaline earth metal oxide RO is equal to or greater than the sum of the molar proportions of B2O3 and Al2O3, and the composition of the glass is also characterized by the following constituent phases constituting the glass:
[0328]
[0329]
[0330] And wherein the decimal logarithm of the hydrogen permeability p calculated according to formula (10) is less than -21500.
[0331] manufacture
[0332] The present invention also relates to a method for producing a hydrogen storage device, in particular a hydrogen storage device according to the present invention. The method preferably comprises the following steps:
[0333] forming the composite material, in particular a composite material or a composite material, into a wall having one or more openings,
[0334] - Introducing a valve into each of said openings.
[0335] The present invention also relates to a method for producing a composite material, such as a composite material or a composite material, in particular a composite material according to the present invention, such as a composite material or a composite material according to the present invention. The method preferably comprises the following steps:
[0336] Provide barrier materials,
[0337] Provide reinforcement materials
[0338] • Connecting barrier material and reinforcing material to form a combined material, in particular to form a material composite or a composite material.
[0339] In the case of composite materials, the connection can be carried out, for example, by hot pressing, rolling or hot isostatic pressing (in particular three-dimensionally on the core) or a combination of two or more thereof.
[0340] In the case of material composites, adhesive solutions can also be used. In particular, the reinforcing material, such as carbon fiber reinforced plastic (CFRP), can be connected to the barrier material using a connecting agent, in particular an adhesive, for example by means of one or more organic polymers, in particular resins. For example, a tube made of barrier material can be wrapped on the outside with the reinforcing material in the form of resin. Curing can also be carried out at elevated temperature, preferably at a temperature below 250° C.
[0341] If bulk materials (eg glass powder) are used as a linker for the barrier material, they can be applied, for example, in the form of a particle suspension (glass powder in / with a binder solution, eg polyvinyl butyral (PVB) in ethanol (EtOH) solution) or as a sol-gel.
[0342] In addition to impregnating the reinforcement material with sol-gel, spraying can also be used.
[0343] The outside of the tube can then be wrapped again. However, the inside can be coated as with resin, mainly by lamination technology.
[0344] In the case of particles and / or sol-gels, preferably one or more tempering steps are provided, such as sol-gel conversion, binder burnout and / or densification of the composite. Annealing is preferably carried out at a temperature below the glass transition temperature Tg of the barrier material. Externally winding the tube and tempering can also be carried out simultaneously.
[0345] In order to achieve a particularly intimate internal connection of the barrier material and the reinforcing material, the barrier material may preferably first be subjected to a surface treatment, in particular a chemical and / or physical pretreatment (for example with plasma) or the application of an adhesion promoter (in particular a primer).
[0346] When using carbon fibers, the tendency to degrade at high temperatures in normal atmosphere must be taken into account. It may be preferred to carry out the processing or heat treatment under protective gas.
[0347] According to the present invention, the method for manufacturing the glass or glass product of the present invention also comprises the following steps:
[0348] Melting the glass tube material
[0349] Molded glass products,
[0350] Cool the glass.
[0351] The shaping of the glass may include a drawing process, in particular a tube drawing process or a drawing process for sheet glass or fibers. The cooling may be active cooling using a coolant, such as a cooling fluid, or may be performed by passive cooling.
[0352] Particularly preferably, the shaping comprises a planar glass method, such as a drawing method. Such a method can be used to obtain a glass layer or a glass film. Such a design of the glass article or glass is particularly advantageous for achieving the desired low hydrogen permeability.
[0353] The present invention also provides a method for manufacturing glass by a coating method.
[0354] The invention also relates to a method for producing a composite material, in particular a material composite or a composite material containing or consisting of carbon or silicon carbide fiber-reinforced glass, using the glass according to the invention for a glass matrix.
[0355] Uses and glass products
[0356] The present invention also includes glass articles formed from the glass, such as glass tubes.
[0357] The present invention also relates to a glass article comprising or consisting of the glass according to the invention. In particular when used in a barrier material or as a barrier material, the glass article is planar and therefore not fibrous. A fibrous design of the glass article would be associated with an increase in the hydrogen permeability, which is to be avoided according to the invention. On the contrary, the hydrogen permeability should be lower. Therefore, the glass article according to the invention is preferably non-fibrous. On the contrary, a planar design of the glass article is preferred. The glass article is preferably designed in layers, for example in the form of a glass layer or a glass film. Therefore, the glass article is preferably in the form of a glass layer, in particular in the form of a glass film. The glass article is preferably a glass layer or a glass film.
[0358] The invention also relates to a composite material, such as a material composite, in particular a layer composite, which contains or consists of a glass according to the invention and at least one further layer. The further layer can contain carbon fibers and / or silicon carbide fibers.
[0359] The invention also relates to the use of the glass according to the invention for glass layers.
[0360] The present invention further relates to the use of the glass or glass product according to the invention in a hydrogen storage device, in particular the hydrogen storage device according to the invention, or as a barrier material for the wall of a hydrogen storage device.
[0361] The present invention further relates to the use of the glass or glass product of the present invention in or as a barrier material of a composite material, in particular a barrier material of the composite material of the present invention, which composite material comprises a barrier material and a reinforcing material.
[0362] The invention also relates to the use of the glass according to the invention for fiber-reinforced glass.
[0363] The invention further relates to the use of the glass or composite material according to the invention, in particular a material composite or a composite material or a layer composite, in or as a hydrogen store, in particular as a barrier material for molecular hydrogen.
[0364] The hydrogen storage device of the present invention (especially its wall) preferably comprises the composite material of the present invention, especially a composite material or a composite material. The hydrogen storage device of the present invention preferably comprises the glass of the present invention, especially in the composite material, especially the composite material or the composite material of the wall or as a barrier material of the composite material, especially the composite material or the composite material of the wall.
[0365] The combination material, in particular the composite material or the composite material according to the invention preferably comprises the glass according to the invention. The barrier material of the combination material, in particular the composite material or the composite material according to the invention preferably comprises the glass according to the invention or consists of the glass according to the invention.
[0366] Description of the drawings
[0367] Figure 1 A preferred embodiment of a hydrogen storage device 11 of the present invention is shown, which has a wall made of a composite material including an inner barrier layer 13 (i.e. facing the cavity 12) made of a barrier material and an outer reinforcement layer 14 made of a reinforcement material. The reinforcement layer 14 is arranged continuously around the circumference of the barrier layer 13. The hydrogen storage device includes two valves 15 and 16 arranged on opposite sides.
[0368] Figure 2 Another preferred embodiment of the invention is shown in the form of a hydrogen storage device 21 having a cavity 22 and a wall, the hydrogen storage device comprising an inner barrier layer 23 made of a barrier material and an outer reinforcement layer 24 made of a reinforcement material. Figure 1 On the contrary, Figure 2 In the embodiment, the reinforcing layer 24 is only arranged on the long side of the wall. No reinforcing layer 24 is arranged on the short side, and the valves 25 and 26 are also located on the short side. Here, the wall is formed only by the barrier layer 23.
[0369] Figure 3 Two further embodiments of the invention are shown in the form of a hydrogen storage 31a and a hydrogen storage 31b. The two hydrogen storages 31a and 31b are bottle-shaped and include cavities (32a, 32b) in which hydrogen can be stored. Valves 35a and 35b are arranged at the top, i.e. at opposite sides of the bottom (37a, 37b) below. In the hydrogen storage ( 31a ) Figure 3 In the left side of the figure, the reinforcing layer 34a is arranged continuously around the barrier layer 33a. In contrast, the hydrogen storage 31b is designed so that no reinforcing layer 34b is provided in the upper region, especially near the valve 35b, so that the wall there is formed only by the barrier layer 33b.
[0370] Example
[0371] The present invention is further described below by way of example using selected examples.
[0372] Hydrogen storage
[0373] In a preferred embodiment of the present invention, the hydrogen storage device of the present invention has a wall portion made of a composite material, which surrounds a cavity in which hydrogen can be stored. The composite material includes an inner barrier layer made of a barrier material and an outer reinforcement layer made of a reinforcement material. The barrier layer is in the form of a planar material. The reinforcement layer is continuously arranged around the barrier layer. The hydrogen storage device includes two valves arranged on opposite sides.
[0374] According to another preferred embodiment of the present invention, the hydrogen storage is provided with a cavity for storing hydrogen and a wall portion, the wall portion comprising an inner barrier layer made of a barrier material and an outer reinforcement layer made of a reinforcement material. In this embodiment, the reinforcement layer is only provided on the long side of the wall portion. There is no reinforcement layer on the short side where the valve is located. The wall portion there is formed only by the barrier layer.
[0375] According to another embodiment of the present invention, the hydrogen storage device is designed to be bottle-shaped and further comprises a cavity in which hydrogen can be stored. The valve is arranged at the top, i.e., at the opposite side of the bottom below. The reinforcement layer can be arranged continuously around the barrier layer. However, the hydrogen storage device can also be designed such that no reinforcement layer is arranged in the upper region, in particular near the valve, so that the wall there is formed only by the barrier layer.
[0376] Combined Materials
[0377] A particularly preferred composite material of the present invention is composed of a barrier material and a reinforcing material. In particular, the composite material is a layered composite made of a barrier material and a reinforcing material. Exemplary barrier materials and exemplary reinforcing materials are described in more detail below.
[0378] Barrier materials
[0379] Glass is particularly suitable as a barrier material.
[0380] The following table lists the compositions of some glasses in the form of constituent phases and the values of density, CTE, bulk density and H2 permeability / mol / (m·s·Pa) calculated according to the present invention.
[0381]
[0382] The materials shown are basically suitable as barrier materials. However, the hydrogen permeability is relatively high. Particularly problematic is the clear tendency for materials with lower hydrogen permeability to have higher CTE and vice versa. Materials that are particularly suitable for combination materials with the required reinforcement material due to their average CTE are not optimal with regard to their hydrogen permeability.
[0383] The materials shown in the table below are preferred because they combine a suitable CTE with very low hydrogen permeability.
[0384]
[0385] Reinforcement Materials
[0386] The reinforcing material is in particular a fibrous material, preferably carbon fibers and / or silicon carbide fibers. Therefore, the composite material is preferably fiber-reinforced glass.
[0387] Reference numerals list
[0388] 11, 21, 31a, 31b Hydrogen storage
[0389] 12, 22, 32a, 32b Cavity
[0390] 12, 23, 33a, 33b Barrier layer
[0391] 14, 24, 34a, 34b Reinforcement layer
[0392] 15, 16, 25, 26, 35a, 35b valves
[0393] 37a, 37b bottom.
Claims
1. A hydrogen storage device, comprising a cavity and a wall surrounding the cavity, ·in, The wall portion comprises a composite material, wherein the composite material comprises a barrier material and a reinforcing material, wherein the barrier material is in particular a planar material. wherein the wall has a thickness of at most 50 mm, and wherein the decimal logarithm of the hydrogen permeability p of the wall is less than -20,000, in particular at a temperature of 473 K.
2. The hydrogen storage device according to claim 1, wherein: The hydrogen storage device is a mobile hydrogen storage device, in particular a hydrogen tank which is part of a vehicle.
3. The hydrogen storage device according to claim 1, wherein: The wall portion has at least one opening.
4. The hydrogen storage device according to claim 1, wherein: The total thickness of the wall varies within the range of 0.1 to 10 mm.
5. The hydrogen storage device according to claim 1, wherein: The wall has an inner layer and an outer layer.
6. Hydrogen storage according to at least one of the preceding claims, wherein The hydrogen storage includes one or more valves.
7. A composite material, in particular according to at least one of the preceding claims, comprising a barrier material and a reinforcing material, wherein: In the range of 20° C. to 300° C., the difference in average linear thermal expansion coefficients of the barrier material and the reinforcement material is at most 10.0 ppm / K.
8. The composite material according to claim 7, wherein: The barrier material comprises glass and / or wherein the reinforcement material comprises carbon fiber and / or silicon carbide fiber.
9. The composite material according to at least one of claims 7 and 8, wherein: The barrier material is in layered form.
10. The composite material according to claim 9, wherein: The barrier material is in the form of a film.
11. The composite material according to at least one of claims 7 to 10, wherein: The barrier material comprises glass having the following components given in the specified proportions (in Mol %): wherein the sum of the molar proportions of alkali metal oxides R2O and alkaline earth metal oxides RO is equal to or greater than the sum of the molar proportions of B2O3 and Al2O3, wherein the composition of the glass is characterized by the following constituent phases of the glass: And wherein the decimal logarithm of the hydrogen permeability p calculated according to formula (10) is less than -20000.
12. The barrier material according to claim 11, wherein: The glass has a CTE in the range of 3.5 to 9.5 ppm / K calculated according to formula (3), and / or According to formula (1), the range is 2.20 to 2.70 g / cm 3 The density ρ in the range of , and / or A bulk density χ of at least 0.49 calculated according to formula (2), and / or an elastic modulus E of at least 60 GPa calculated according to formula (8).
13. The barrier material according to at least one of claims 11 to 12, wherein The content of residues in the glass is at most 3.0 mol%, and / or the content of MgO is greater than the content of Li2O, and / or The proportion of Malinkoit is at least 1.0 Mol % and / or the proportion of cordierite is at least 1.0 Mol % and / or the sum of the proportions of cordierite and Malinkoit is in the range of 50 to 100 Mol %.
Citation Information
Patent Citations
borosilicate glass with low brittleness and high intrinsic strength, its production and use
DE102014119594A1
Glasses with improved ion exchangeability and thermal expansion
DE102017102482B4
Glasses having improved hydrolytic and lye resistance
EP3473604B1